Conductive particle, conductive material, and connection structure
Conductive particles with a substrate and a surface conductive portion, featuring a solder portion with limited surface area coverage, address the issue of particle aggregation in solder pastes, enhancing conduction reliability and connection efficiency for thinner and smaller electronic devices.
Patent Information
- Application Number
- JP2024231823
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-06-13
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-06-12
AI Technical Summary
Conventional solder pastes used for connecting substrates to electronic components often experience particle aggregation, which complicates the connection process, especially as electronic devices become thinner and smaller, requiring narrower pitches.
The development of conductive particles with a substrate particle and a conductive portion on its surface, where the conductive portion includes a component capable of metal diffusion at or below 400°C or is melt deformable at or below 400°C, and has a solder portion with a limited surface area coverage of 99% or less on the substrate particle.
These conductive particles effectively suppress the aggregation of conductive particles, enabling improved conduction reliability and allowing for connections with reduced connection resistance, even at smaller device dimensions.
Smart Images

Figure 2025063102000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive particle having a conductive portion disposed on the surface of a base particle. The present invention also relates to a conductive material and a connection structure using the conductive particle. [Background technology]
[0002] There is a widely known electronic component in which a connector (first component) and a printed wiring board (second component) are electrically connected by pins. In the electronic component, the pins are inserted into through holes or the like formed in the printed wiring board, or are directly disposed on electrodes on the wiring board, and are connected to the printed wiring board by soldering.
[0003] The following Patent Document 1 discloses a connection structure for electronic components in which an alignment member (50) is used to align the other ends of a plurality of pins (20), one end of which is connected to a first member (10), and connect the other ends to a second member (30). In the connection structure for electronic components, the alignment member (50) aligns the pins (20) at the outer periphery in the axial direction (A), and then rotates with the axial direction (A) as a reference to detach and remove the alignment member (50) from the pins (20). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2000-294997 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, electronic devices have become thinner and smaller. For this reason, it is difficult to accommodate narrower pitches when connecting a substrate and electronic components using conventional pins. For this reason, solder paste or the like is sometimes used to electrically connect the substrate and electronic components.
[0006] However, in conventional solder pastes, the solder particles may sometimes clump together.
[0007] An object of the present invention is to provide a conductive particle capable of effectively suppressing the occurrence of aggregation between the conductive particles. Another object of the present invention is to provide a conductive material and a connection structure using the conductive particle. [Means for solving the problem]
[0008] According to a broad aspect of the present invention, there is provided a conductive particle comprising a base particle and a conductive portion disposed on a surface of the base particle, the conductive portion containing a component capable of metal diffusion at 400°C or less, or the conductive portion being melt deformable at 400°C or less, the conductive portion having a solder portion, and an area of the portion in which the solder portion is located being 99% or less of a total surface area (100%) of the base particle.
[0009] In a specific aspect of the conductive particle according to the present invention, the solder portion is a solder grain.
[0010] In a specific aspect of the conductive particles according to the present invention, the material of the solder grains includes an alloy containing tin, is pure tin, or contains tin in a state different from the alloy containing tin and different from pure tin.
[0011] In a specific aspect of the conductive particles according to the present invention, the material of the solder grains is pure tin.
[0012] In a specific aspect of the conductive particle according to the present invention, the height of the solder grain is not less than 10 nm and not more than 10 μm.
[0013] In a specific aspect of the conductive particle according to the present invention, the aspect ratio of the solder grain is 0.05 or more and 5 or less.
[0014] In a specific aspect of the conductive particle according to the present invention, the conductive particle has a metal colloid deposit or a metal film on the outer surface of the solder grain.
[0015] In a specific aspect of the conductive particle according to the present invention, the area of the portion where the metal colloid deposit or the metal film is present is 5% or more and 100% or less of the total surface area (100%) of the solder grain.
[0016] In a specific aspect of the conductive particles according to the present invention, the metal species of the metal colloid deposit or the metal species of the metal film is nickel, cobalt, lead, gold, zinc, palladium, copper, silver, bismuth, or indium.
[0017] In a specific aspect of the conductive particles according to the present invention, the particle diameter is 0.5 μm or more and 500 μm or less.
[0018] According to a broad aspect of the invention, there is provided a conductive material comprising conductive particles and a binder, the conductive particles being as described above.
[0019] According to a broad aspect of the present invention, there is provided a connection structure comprising a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection portion connecting the first connection target member and the second connection target member, wherein the connection portion is formed from conductive particles or from a conductive material containing the conductive particles and a binder, the conductive particles are the conductive particles described above, and the first electrode and the second electrode are electrically connected by the conductive particles. Effect of the Invention
[0020] The conductive particle according to the present invention comprises a base particle and a conductive portion disposed on the surface of the base particle. In the conductive particle according to the present invention, the conductive portion contains a component capable of metal diffusion at 400°C or less, or the conductive portion is melt deformable at 400°C or less. In the conductive particle according to the present invention, the conductive portion has a solder portion. In the conductive particle according to the present invention, the area of the portion where the solder portion is present is 99% or less of the total surface area (100%) of the base particle. Since the conductive particle according to the present invention has the above configuration, it is possible to effectively suppress the occurrence of aggregation between the conductive particles. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing a conductive particle according to a fourth embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view showing a conductive particle according to a fifth embodiment of the present invention. [Figure 6] FIG. 6 is a cross-sectional view showing a conductive particle according to a sixth embodiment of the present invention. [Figure 7] FIG. 7 is a cross-sectional view showing a conductive particle according to a seventh embodiment of the present invention. [Figure 8] FIG. 8 is a cross-sectional view showing a conductive particle according to an eighth embodiment of the present invention. [Figure 9] FIG. 9 is a front cross-sectional view that illustrates a connection structure using conductive particles according to a third embodiment of the present invention. [Figure 10] FIG. 10 is an enlarged front cross-sectional view that illustrates a schematic view of a connection portion between a conductive particle and an electrode in the connection structure shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will be described in detail below.
[0023] (Conductive particles) The conductive particle according to the present invention comprises a base particle and a conductive part arranged on the surface of the base particle. In the conductive particle according to the present invention, the conductive part contains a component capable of metal diffusion at 400° C. or less, or the conductive part is melt deformable at 400° C. or less. In the conductive particle according to the present invention, the conductive part may contain a component capable of metal diffusion at 400° C. or less, and the conductive part may be melt deformable at 400° C. or less. In the conductive particle according to the present invention, the conductive part may contain a component capable of metal diffusion at 400° C. or less, and the conductive part may be melt deformable at 400° C. or less. In the conductive particle according to the present invention, the conductive part has a solder part. In the conductive particle according to the present invention, the area of the part where the solder part is present is 99% or less of the total surface area of the base particle (100%).
[0024] In the present invention, metal diffusion refers to the diffusion of metal atoms in conductive parts or connecting parts due to heat, pressure, deformation, or the like.
[0025] In the present invention, the term "melt deformation" refers to a state in which a part or all of the components are melted and the material becomes easily deformed by an external pressure.
[0026] Since the conductive particles according to the present invention have the above-mentioned configuration, the occurrence of aggregation between the conductive particles can be effectively suppressed.
[0027] In recent years, electronic devices have become thinner and smaller. For this reason, it is difficult to accommodate narrower pitches when connecting a substrate and electronic components using conventional pins. For this reason, solder paste or the like is sometimes used to electrically connect the substrate and electronic components.
[0028] However, in conventional solder pastes, the solder particles may sometimes clump together.
[0029] The present inventors have found that the use of specific conductive particles can suppress the aggregation of conductive particles. In the present invention, the conductive part contains a component capable of metal diffusion at 400° C. or less, or the conductive part is meltable and deformable at 400° C. or less. In the conductive particle according to the present invention, the conductive part has a solder part. The solder part is preferably a solder grain. In the conductive particle according to the present invention, the conductive part can form a metallic bond with a joint part such as an electrode, and the solder part (solder grain) can form a metallic bond with a joint part such as an electrode. Therefore, a conductive characteristic that is dramatically superior to conventional physical contact can be obtained. In addition, in the conductive particle according to the present invention, since the solder part (solder grain) can form a metallic bond with a joint part such as an electrode, it is not necessary to melt the entire conductive part during bonding. As a result, in the present invention, even if the thickness of the conductive part is relatively thin, the reliability of conduction between the electrodes can be improved. In addition, in the present invention, since it is not necessary to increase the thickness of the conductive part, it is possible to effectively suppress the aggregation of conductive particles.
[0030] In the present invention, the use of specific conductive particles greatly contributes to obtaining the above-mentioned effects.
[0031] The temperature at which the components of the conductive part can undergo metal diffusion and the melting deformation temperature of the conductive part can be achieved by selecting the material of the conductive part. For example, by forming a solder part using solder or a solder alloy as the material of the conductive part, it is easy to set the temperature at which the components of the conductive part can undergo metal diffusion and the melting deformation temperature of the conductive part to 400° C. or less. In the conductive particle, the conductive part has a solder part. The conductive part may be a solder part.
[0032] The state of metal diffusion in the conductive portion is evaluated as follows.
[0033] A conductive paste containing 10% by weight of conductive particles is prepared.
[0034] A transparent glass substrate having a copper electrode on its upper surface and a semiconductor chip having a gold electrode on its lower surface are prepared.
[0035] A conductive paste is applied onto the transparent glass substrate to form a conductive paste layer. Next, the semiconductor chip is laminated on the conductive paste layer so that the electrodes face each other. Then, a pressure heating head is placed on the upper surface of the semiconductor chip while adjusting the temperature of the head so that the temperature of the conductive paste layer is 250°C, and a pressure of 0.5 MPa is applied to harden the conductive paste layer at 250°C to obtain a connection structure.
[0036] The connection structure is mechanically polished so as to pass through the vicinity of the center thereof, and a cross section of the conductive particle is cut out using an ion milling device. In order to facilitate mechanical polishing of the connection structure, the connection structure may be embedded in a resin, and the connection structure embedded in the resin may be mechanically polished.
[0037] Next, using a transmission electron microscope (FE-TEM), the contact areas between the conductive particles and the copper electrode and gold electrode are subjected to line analysis or element mapping using an energy dispersive X-ray analyzer (EDX) to observe the diffusion state of the metal.
[0038] By observing the diffusion state of the metal, it is possible to confirm that the outer periphery of the conductive particles is metal-diffused into the copper electrode and the gold electrode.
[0039] Furthermore, by mapping the diffusion state of the metal, the contact ratio between the periphery of the conductive particle and the copper electrode and the gold electrode can be calculated, which also makes it possible to carry out quantification.
[0040] The melting deformation temperature of the conductive portion is evaluated as follows.
[0041] The melting deformation temperature of the conductive part can be measured using a differential scanning calorimeter ("DSC-6300" manufactured by Yamato Scientific Co., Ltd.) The measurement is performed using 15 g of conductive particles under the following measurement conditions: temperature rise range 30°C to 500°C, temperature rise rate 5°C / min, and nitrogen purge amount 5 ml / min.
[0042] Next, it is confirmed that the conductive part is melted at the melting temperature obtained in the above measurement. 1 g of conductive particles is placed in a container and placed in an electric furnace. The electric furnace is set to the same temperature as the melting temperature obtained in the above measurement, and heated in a nitrogen atmosphere for 10 minutes. Thereafter, the heated conductive particles are removed from the electric furnace, and the molten state (or solidified state after melting) of the conductive part is confirmed using a scanning electron microscope. Note that the conductive part may be melted and deformed by melting a partial area of the conductive part, such as the solder part (solder grains).
[0043] In the conductive particle according to the present invention, the area of the portion where the solder part is present (solder part coverage) is 99% or less out of the total surface area of the base particle (100%). The area of the portion where the solder part is present (solder part coverage) out of the total surface area of the base particle (100%) is preferably 95% or less, more preferably 90% or less, even more preferably 85% or less, and particularly preferably 70% or less. The area of the portion where the solder part is present (solder part coverage) out of the total surface area of the base particle (100%) is preferably 5% or more, more preferably 30% or more, and even more preferably 60% or more. When the coverage (solder part coverage) is equal to or greater than the lower limit and equal to or less than the upper limit, the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the coverage (solder part coverage) is equal to or greater than the lower limit, a metal bond can be more easily formed between the solder part and the joint part of the electrode or the like.
[0044] The area of the portion where the solder part is located (solder part coverage rate) out of the total surface area of the base particle (100%) can be calculated by performing SEM-EDX analysis of the cross section of the conductive particle to perform elemental mapping and image analysis.
[0045] The particle diameter of the conductive particles is preferably 0.5 μm or more, more preferably 1 μm or more, and is preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle diameter of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the contact area between the conductive particles and the electrode can be sufficiently large, and the conductive particles are less likely to aggregate when forming the conductive portion, and the conductive portion is less likely to peel off from the surface of the base particle.
[0046] The particle diameter of the conductive particles is preferably an average particle diameter, and is preferably a number average particle diameter. The particle diameter of the conductive particles is, for example, obtained by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average particle diameter of each conductive particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or an optical microscope, the particle diameter of each conductive particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary conductive particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each conductive particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the conductive particles is preferably calculated using a particle size distribution measuring device.
[0047] The conductive particles preferably have a particle size variation coefficient (CV value) of 10% or less, more preferably 5% or less. When the conductive particles have a particle size variation coefficient of the upper limit or less, the contact area between the conductive particles and the electrode can be sufficiently large.
[0048] The coefficient of variation (CV value) can be measured as follows.
[0049] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of the particle size of the conductive particles Dn: Average particle size of conductive particles
[0050] The shape of the conductive particles is not particularly limited, and may be spherical, may be a shape other than spherical, or may be flat or the like.
[0051] The present invention will now be described in detail with reference to the drawings.
[0052] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention.
[0053] 1 includes a base particle 2 and a conductive portion 3 disposed on the surface of the base particle 2. In the first embodiment, the conductive portion 3 is in contact with the surface of the base particle 2. The conductive particle 1 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 3.
[0054] The conductive part 3 as a whole has a first conductive part 3A arranged on the surface of the base particle 2 and a second conductive part (solder part) 3B arranged on the surface of the first conductive part 3A. The first conductive part 3A is arranged on the surface of the base particle 2. The first conductive part 3A is arranged between the base particle 2 and the second conductive part (solder part) 3B. The first conductive part 3A is in contact with the base particle 2. The second conductive part (solder part) 3B is in contact with the first conductive part 3A. Therefore, the first conductive part 3A is arranged on the surface of the base particle 2, and the second conductive part (solder part) 3B is arranged on the surface of the first conductive part 3A. In the conductive particle, the base particle may be completely covered by the first conductive part, or may not be completely covered. The base particle may have a portion that is not covered by the first conductive part. The first conductive portion and the second conductive portion (solder portion) may be formed as different conductive portions or may be formed as the same conductive portion. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably a solder grain described below. In the conductive particle, it is preferable that the first conductive portion is disposed on the surface of the base particle, and the solder grains are disposed on the surface of the first conductive portion.
[0055] In the conductive particle 1, the conductive part 3 includes a component capable of metal diffusion at 400° C. or less, or the conductive part 3 is melt-deformable at 400° C. or less. The conductive part 3 may include a component capable of metal diffusion at 400° C. or less, or the conductive part 3 may be melt-deformable at 400° C. or less. The conductive part 3 may include a component capable of metal diffusion at 400° C. or less, and the conductive part 3 may be melt-deformable at 400° C. or less. In the conductive particle 1, the second conductive part 3B (solder part) is a component capable of metal diffusion at 400° C. or less. In the conductive particle 1, the second conductive part 3B (solder part) is melt-deformable at 400° C. or less. In the conductive particle, the first conductive part may be a component capable of metal diffusion at 400° C. or less, or the first conductive part may be melt-deformable at 400° C. or less. In the conductive particle, the first conductive portion and the second conductive portion (solder portion) may be components that can undergo metal diffusion at 400°C or less, and the first conductive portion and the second conductive portion (solder portion) may be melt-deformable at 400°C or less.
[0056] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention.
[0057] 2 includes a base particle 2 and a conductive portion 12 disposed on the surface of the base particle 2. In the second embodiment, the conductive portion 12 is in contact with the surface of the base particle 2. The conductive particle 11 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 12.
[0058] The only difference between the conductive particle 1 and the conductive particle 11 is the first conductive portion. That is, the conductive particle 1 has a first conductive portion 3A having a single layer structure, whereas the conductive particle 11 has a first conductive portion having a two-layer structure composed of a conductive portion 12A 1a and a conductive portion 12B 1b.
[0059] The conductive portion 12 as a whole has a conductive portion 12A of 1a arranged on the surface of the base particle 2, a conductive portion 12B of 1b arranged on the surface of the conductive portion 12A of 1a, and a second conductive portion (solder portion) 12C arranged on the surface of the conductive portion 12B of 1b. The conductive portion 12A of 1a is arranged on the surface of the base particle 2. The conductive portion 12B of 1b is arranged on the surface of the conductive portion 12A of 1a. The conductive portion 12A of 1a and the conductive portion 12B of 1b are arranged between the base particle 2 and the second conductive portion (solder portion) 12C. The conductive portion 12A of 1a is in contact with the base particle 2. The second conductive portion (solder portion) 12C is in contact with the conductive portion 12B of 1b. Therefore, the conductive portion 12A of 1a is disposed on the surface of the base particle 2, the conductive portion 12B of 1b is disposed on the surface of the conductive portion 12A of 1a, and the second conductive portion (solder portion) 12C is disposed on the surface of the conductive portion 12B of 1b. In the conductive particle, the base particle may be completely covered by the conductive portion 1a and the conductive portion 1b, or may not be completely covered. The base particle may have a portion that is not covered by the conductive portion 1a and the conductive portion 1b. The conductive portion 1a, the conductive portion 1b, and the second conductive portion (solder portion) may be formed as different conductive portions, or may be formed as the same conductive portion. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably a solder grain described later. In the conductive particle, it is preferable that the conductive portion 1a is arranged on the surface of the base particle, the conductive portion 1b is arranged on the surface of the conductive portion 1a, and the solder grains are arranged on the surface of the conductive portion 1b.
[0060] In the conductive particle 11, the conductive part 12 includes a component capable of metal diffusion at 400° C. or less, or the conductive part 12 is melt-deformable at 400° C. or less. The conductive part 12 may include a component capable of metal diffusion at 400° C. or less, or the conductive part 12 may be melt-deformable at 400° C. or less. The conductive part 12 may include a component capable of metal diffusion at 400° C. or less, and the conductive part 12 may be melt-deformable at 400° C. or less. In the conductive particle 11, the second conductive part 12C (solder part) is a component capable of metal diffusion at 400° C. or less. In the conductive particle 11, the second conductive part 12C (solder part) is melt-deformable at 400° C. or less. In the conductive particle, the conductive part 1a or the conductive part 1b may be a component capable of metal diffusion at 400° C. or less, or the conductive part 1a or the conductive part 1b may be melt-deformable at 400° C. or less. In the above conductive particles, the conductive portion 1a, the conductive portion 1b and the second conductive portion (solder portion) may be components capable of metal diffusion at 400°C or less, and the conductive portion 1a, the conductive portion 1b and the second conductive portion (solder portion) may be melt-deformable at 400°C or less.
[0061] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention.
[0062] 3 includes a base particle 2 and a conductive portion 22 disposed on the surface of the base particle 2. In the third embodiment, the conductive portion 22 is in contact with the surface of the base particle 2. The conductive particle 21 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 22.
[0063] The only difference between the conductive particle 1 and the conductive particle 21 is the shape of the second conductive portion (solder portion). That is, in the conductive particle 1, the shape of the second conductive portion (solder portion) 3B is a part of a sphere, whereas in the conductive particle 21, the shape of the second conductive portion (solder portion) 22B is needle-like and has a paraboloid of revolution.
[0064] The conductive portion 22 as a whole has a first conductive portion 22A arranged on the surface of the base particle 2 and a second conductive portion (solder portion) 22B arranged on the surface of the first conductive portion 22A. The first conductive portion 22A is arranged on the surface of the base particle 2. The first conductive portion 22A is arranged between the base particle 2 and the second conductive portion (solder portion) 22B. The first conductive portion 22A is in contact with the base particle 2. The second conductive portion (solder portion) 22B is in contact with the first conductive portion 22A. Therefore, the first conductive portion 22A is arranged on the surface of the base particle 2, and the second conductive portion (solder portion) 22B is arranged on the surface of the first conductive portion 22A. In the conductive particle, the base particle may be completely covered by the first conductive portion, or may not be completely covered. The base particle may have a portion that is not covered by the first conductive portion. The first conductive portion and the second conductive portion (solder portion) may be formed as different conductive portions or may be formed as the same conductive portion. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably a solder grain, which will be described later.
[0065] In the conductive particle 21, the conductive part 22 includes a component capable of metal diffusion at 400° C. or less, or the conductive part 22 is melt-deformable at 400° C. or less. The conductive part 22 may include a component capable of metal diffusion at 400° C. or less, or the conductive part 22 may be melt-deformable at 400° C. or less. The conductive part 22 may include a component capable of metal diffusion at 400° C. or less, and the conductive part 22 may be melt-deformable at 400° C. or less. In the conductive particle 21, the second conductive part 22B (solder part) is a component capable of metal diffusion at 400° C. or less. In the conductive particle 21, the second conductive part 22B (solder part) is melt-deformable at 400° C. or less. In the conductive particle, the first conductive part may be a component capable of metal diffusion at 400° C. or less, or the first conductive part may be melt-deformable at 400° C. or less. In the conductive particle, the first conductive portion and the second conductive portion (solder portion) may be components that can undergo metal diffusion at 400°C or less, and the first conductive portion and the second conductive portion (solder portion) may be melt-deformable at 400°C or less.
[0066] FIG. 4 is a cross-sectional view showing a conductive particle according to a fourth embodiment of the present invention.
[0067] 4 includes a base particle 2 and a conductive portion 32 disposed on the surface of the base particle 2. In the fourth embodiment, the conductive portion 32 is in contact with the surface of the base particle 2. The conductive particle 31 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 32.
[0068] The only difference between conductive particle 21 and conductive particle 31 is the conductive portion. That is, in conductive particle 21, conductive portion 22 is formed of a first conductive portion 22A and a second conductive portion (solder portion) 22B, whereas in conductive particle 31, conductive portion 32 is formed of a first conductive portion 32A, a second conductive portion (solder portion) 32B, and a third conductive portion 32C.
[0069] The conductive portion 32 as a whole has a first conductive portion 32A arranged on the surface of the base particle 2, a second conductive portion (solder portion) 32B arranged on the surface of the first conductive portion 32A, and a third conductive portion 32C arranged on the surfaces of the first conductive portion 32A and the second conductive portion (solder portion) 32B. The first conductive portion 32A is arranged on the surface of the base particle 2. The third conductive portion 32C is arranged on the surfaces of the first conductive portion 32A and the second conductive portion (solder portion) 32B. The first conductive portion 32A and the second conductive portion (solder portion) 32B are arranged between the base particle 2 and the third conductive portion 32C. The first conductive portion 32A is in contact with the base particle 2. The second conductive portion (solder portion) 32B is in contact with the first conductive portion 32A. The third conductive portion 32C is in contact with the first conductive portion 32A and the second conductive portion (solder portion) 32B. Therefore, the first conductive portion 32A is disposed on the surface of the base particle 2, the second conductive portion (solder portion) 32B is disposed on the surface of the first conductive portion 32A, and the third conductive portion 32C is disposed on the surfaces of the first conductive portion 32A and the second conductive portion (solder portion) 32B. In the conductive particle, the base particle may be completely covered by the first conductive portion or may not be completely covered. The base particle may have a portion that is not covered by the first conductive portion. In the conductive particle, the base particle may be completely covered by the third conductive portion or may not be completely covered. The base particle may have a portion that is not covered by the third conductive portion. The first conductive portion, the second conductive portion (solder portion), and the third conductive portion may be formed as different conductive portions, or may be formed as the same conductive portion. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably a solder grain described below. In the conductive particle, it is preferable that the first conductive portion is disposed on the surface of the base particle, the solder grains are disposed on the surface of the first conductive portion, and the third conductive portion is disposed on the surfaces of the first conductive portion and the solder grains.
[0070] In the conductive particle 31, the conductive part 32 includes a component capable of metal diffusion at 400° C. or less, or the conductive part 32 is melt-deformable at 400° C. or less. The conductive part 32 may include a component capable of metal diffusion at 400° C. or less, or the conductive part 32 may be melt-deformable at 400° C. or less. The conductive part 32 may include a component capable of metal diffusion at 400° C. or less, and the conductive part 32 may be melt-deformable at 400° C. or less. In the conductive particle 31, the second conductive part 32B (solder part) is a component capable of metal diffusion at 400° C. or less. In the conductive particle 31, the second conductive part 32B (solder part) is melt-deformable at 400° C. or less. In the conductive particle, the first conductive part may be a component capable of metal diffusion at 400° C. or less, or the first conductive part may be melt-deformable at 400° C. or less. In the conductive particle, the third conductive portion may be a component capable of metal diffusion at 400° C. or less, and the third conductive portion may be melt deformable at 400° C. or less. In the conductive particle, the first conductive portion, the second conductive portion (solder portion), and the third conductive portion may be components capable of metal diffusion at 400° C. or less, and the first conductive portion, the second conductive portion (solder portion), and the third conductive portion may be melt deformable at 400° C. or less.
[0071] FIG. 5 is a cross-sectional view showing a conductive particle according to a fifth embodiment of the present invention.
[0072] 5 includes a base particle 2, a conductive portion 42 disposed on the surface of the base particle 2, and a metal colloid deposit 43 disposed on the surface of the conductive portion 42. In the fifth embodiment, the conductive portion 42 is in contact with the surface of the base particle 2. The conductive particle 41 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 42.
[0073] The conductive particle 1 and the conductive particle 41 differ only in the presence or absence of a metal colloid precipitate 43. That is, in the conductive particle 1, a metal colloid precipitate is not disposed on the surface of the conductive portion 3, whereas in the conductive particle 41, a metal colloid precipitate 43 is disposed on the surface of the conductive portion 42.
[0074] The conductive portion 42 as a whole has a first conductive portion 42A arranged on the surface of the base particle 2 and a second conductive portion (solder portion) 42B arranged on the surface of the first conductive portion 42A. The first conductive portion 42A is arranged on the surface of the base particle 2. The first conductive portion 42A is arranged between the base particle 2 and the second conductive portion (solder portion) 42B. The first conductive portion 42A is in contact with the base particle 2. The second conductive portion (solder portion) 42B is in contact with the first conductive portion 42A. Therefore, the first conductive portion 42A is arranged on the surface of the base particle 2, and the second conductive portion (solder portion) 42B is arranged on the surface of the first conductive portion 42A. In the conductive particle, the base particle may be completely covered by the first conductive portion, or may not be completely covered. The base particle may have a portion that is not covered by the first conductive portion. The first conductive portion and the second conductive portion (solder portion) may be formed as different conductive portions or may be formed as the same conductive portion. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably a solder grain described below. In the conductive particle, it is preferable that the first conductive portion is disposed on the surface of the base particle, and the solder grains are disposed on the surface of the first conductive portion.
[0075] A metal colloid precipitate 43 is disposed on the surface of the conductive portion 42. The metal colloid precipitate may be disposed only on the surface of the first conductive portion, may be disposed only on the surface of the second conductive portion (solder portion), or may be disposed on the surfaces of the first conductive portion and the second conductive portion (solder portion). The metal colloid precipitate is preferably disposed only on the surface of the second conductive portion (solder portion), and is preferably disposed only on the surface of the solder grain. In the conductive particle, the conductive portion may be completely covered by the metal colloid precipitate, or may not be completely covered. The conductive portion may have a portion that is not covered by the metal colloid precipitate.
[0076] In the conductive particle 41, the conductive part 42 includes a component capable of metal diffusion at 400° C. or less, or the conductive part 42 is melt-deformable at 400° C. or less. The conductive part 42 may include a component capable of metal diffusion at 400° C. or less, or the conductive part 42 may be melt-deformable at 400° C. or less. The conductive part 42 may include a component capable of metal diffusion at 400° C. or less, and the conductive part 42 may be melt-deformable at 400° C. or less. In the conductive particle 41, the second conductive part 42B (solder part) is a component capable of metal diffusion at 400° C. or less. In the conductive particle 41, the second conductive part 42B (solder part) is melt-deformable at 400° C. or less. In the conductive particle, the first conductive part may be a component capable of metal diffusion at 400° C. or less, or the first conductive part may be melt-deformable at 400° C. or less. In the conductive particle, the first conductive portion and the second conductive portion (solder portion) may be components that can undergo metal diffusion at 400°C or less, and the first conductive portion and the second conductive portion (solder portion) may be melt-deformable at 400°C or less.
[0077] FIG. 6 is a cross-sectional view showing a conductive particle according to a sixth embodiment of the present invention.
[0078] 6 includes a base particle 2, a conductive portion 52 disposed on the surface of the base particle 2, and a metal colloid deposit 53 disposed on the surface of the conductive portion 52. In the sixth embodiment, the conductive portion 52 is in contact with the surface of the base particle 2. The conductive particle 51 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 52.
[0079] The conductive particle 11 and the conductive particle 51 differ only in the presence or absence of a metal colloid precipitate 53. That is, in the conductive particle 11, a metal colloid precipitate is not disposed on the surface of the conductive portion 12, whereas in the conductive particle 51, a metal colloid precipitate 53 is disposed on the surface of the conductive portion 52.
[0080] The conductive portion 52 as a whole has a conductive portion 52A of 1a arranged on the surface of the base particle 2, a conductive portion 52B of 1b arranged on the surface of the conductive portion 52A of 1a, and a second conductive portion (solder portion) 52C arranged on the surface of the conductive portion 52B of 1b. The conductive portion 52A of 1a is arranged on the surface of the base particle 2. The conductive portion 52B of 1b is arranged on the surface of the conductive portion 52A of 1a. The conductive portion 52A of 1a and the conductive portion 52B of 1b are arranged between the base particle 2 and the second conductive portion (solder portion) 52C. The conductive portion 52A of 1a is in contact with the base particle 2. The second conductive portion (solder portion) 52C is in contact with the conductive portion 52B of 1b. Therefore, the conductive portion 52A of 1a is disposed on the surface of the base particle 2, the conductive portion 52B of 1b is disposed on the surface of the conductive portion 52A of 1a, and the second conductive portion (solder portion) 52C is disposed on the surface of the conductive portion 52B of 1b. In the conductive particle, the base particle may be completely covered by the conductive portion of 1a and the conductive portion of 1b, or may not be completely covered. The base particle may have a portion that is not covered by the conductive portion of 1a and the conductive portion of 1b. The conductive portion of 1a, the conductive portion of 1b, and the second conductive portion (solder portion) may be formed as different conductive portions, or may be formed as the same conductive portion. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably a solder grain described later. In the conductive particle, it is preferable that the conductive portion 1a is arranged on the surface of the base particle, the conductive portion 1b is arranged on the surface of the conductive portion 1a, and the solder grains are arranged on the surface of the conductive portion 1b.
[0081] A metal colloid precipitate 53 is disposed on the surface of the conductive portion 52. The metal colloid precipitate may be disposed only on the surface of the conductive portion 1b, may be disposed only on the surface of the second conductive portion (solder portion), or may be disposed on the surfaces of the conductive portion 1b and the second conductive portion (solder portion). The metal colloid precipitate is preferably disposed only on the surface of the second conductive portion (solder portion), and is preferably disposed only on the surface of the solder grain. In the conductive particle, the conductive portion may be completely covered by the metal colloid precipitate, or may not be completely covered. The conductive portion may have a portion that is not covered by the metal colloid precipitate.
[0082] In the conductive particle 51, the conductive portion 52 includes a component capable of metal diffusion at 400° C. or less, or the conductive portion 52 is melt-deformable at 400° C. or less. The conductive portion 52 may include a component capable of metal diffusion at 400° C. or less, or the conductive portion 52 may be melt-deformable at 400° C. or less. The conductive portion 52 may include a component capable of metal diffusion at 400° C. or less, and the conductive portion 52 may be melt-deformable at 400° C. or less. In the conductive particle 51, the second conductive portion 52C (solder portion) is a component capable of metal diffusion at 400° C. or less. In the conductive particle 51, the second conductive portion 52C (solder portion) is melt-deformable at 400° C. or less. In the conductive particle, the conductive portion 1a or the conductive portion 1b may be a component capable of metal diffusion at 400° C. or less, or the conductive portion 1a or the conductive portion 1b may be melt-deformable at 400° C. or less. In the above conductive particles, the conductive portion 1a, the conductive portion 1b and the second conductive portion (solder portion) may be components capable of metal diffusion at 400°C or less, and the conductive portion 1a, the conductive portion 1b and the second conductive portion (solder portion) may be melt-deformable at 400°C or less.
[0083] FIG. 7 is a cross-sectional view showing a conductive particle according to a seventh embodiment of the present invention.
[0084] 7 includes a base particle 2, a conductive portion 62 disposed on the surface of the base particle 2, and a metal film 63 disposed on the surface of the conductive portion 62. In the seventh embodiment, the conductive portion 62 is in contact with the surface of the base particle 2. The conductive particle 61 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 62.
[0085] The conductive particle 1 and the conductive particle 61 differ only in the presence or absence of a metal film 63. That is, in the conductive particle 1, a metal film is not disposed on the surface of the conductive portion 3, whereas in the conductive particle 61, a metal film 63 is disposed on the surface of the conductive portion 62.
[0086] The conductive portion 62 as a whole has a first conductive portion 62A arranged on the surface of the base particle 2 and a second conductive portion (solder portion) 62B arranged on the surface of the first conductive portion 62A. The first conductive portion 62A is arranged on the surface of the base particle 2. The first conductive portion 62A is arranged between the base particle 2 and the second conductive portion (solder portion) 62B. The first conductive portion 62A is in contact with the base particle 2. The second conductive portion (solder portion) 62B is in contact with the first conductive portion 62A. Thus, the first conductive portion 62A is arranged on the surface of the base particle 2, and the second conductive portion (solder portion) 62B is arranged on the surface of the first conductive portion 62A. In the conductive particle, the base particle may be completely covered by the first conductive portion, or may not be completely covered. The base particle may have a portion that is not covered by the first conductive portion. The first conductive portion and the second conductive portion (solder portion) may be formed as different conductive portions or may be formed as the same conductive portion. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably a solder grain described below. In the conductive particle, it is preferable that the first conductive portion is disposed on the surface of the base particle, and the solder grains are disposed on the surface of the first conductive portion.
[0087] A metal film 63 is disposed on the surface of the conductive portion 62. The metal film may be disposed only on the surface of the first conductive portion, may be disposed only on the surface of the second conductive portion (solder portion), or may be disposed on the surfaces of the first conductive portion and the second conductive portion (solder portion). The metal film is preferably disposed only on the surface of the second conductive portion (solder portion), and is preferably disposed only on the surface of the solder grain. In the conductive particle, the conductive portion may or may not be completely covered by the metal film. The conductive portion may have a portion that is not covered by the metal film.
[0088] In the conductive particle 61, the conductive part 62 includes a component capable of metal diffusion at 400° C. or less, or the conductive part 62 is melt-deformable at 400° C. or less. The conductive part 62 may include a component capable of metal diffusion at 400° C. or less, or the conductive part 62 may be melt-deformable at 400° C. or less. The conductive part 62 may include a component capable of metal diffusion at 400° C. or less, and the conductive part 62 may be melt-deformable at 400° C. or less. In the conductive particle 61, the second conductive part 62B (solder part) is a component capable of metal diffusion at 400° C. or less. In the conductive particle 61, the second conductive part 62B (solder part) is melt-deformable at 400° C. or less. In the conductive particle, the first conductive part may be a component capable of metal diffusion at 400° C. or less, or the first conductive part may be melt-deformable at 400° C. or less. In the conductive particle, the first conductive portion and the second conductive portion (solder portion) may be components that can undergo metal diffusion at 400°C or less, and the first conductive portion and the second conductive portion (solder portion) may be melt-deformable at 400°C or less.
[0089] FIG. 8 is a cross-sectional view showing a conductive particle according to an eighth embodiment of the present invention.
[0090] 8 includes a base particle 2, a conductive portion 72 disposed on the surface of the base particle 2, and a metal film 73 disposed on the surface of the conductive portion 72. In the eighth embodiment, the conductive portion 72 is in contact with the surface of the base particle 2. The conductive particle 71 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 72.
[0091] The conductive particle 11 and the conductive particle 71 differ only in the presence or absence of a metal film 73. That is, in the conductive particle 11, a metal film is not disposed on the surface of the conductive portion 12, whereas in the conductive particle 71, a metal film 73 is disposed on the surface of the conductive portion 72.
[0092] The conductive portion 72 as a whole has a conductive portion 72A of 1a arranged on the surface of the base particle 2, a conductive portion 72B of 1b arranged on the surface of the conductive portion 72A of 1a, and a second conductive portion (solder portion) 72C arranged on the surface of the conductive portion 72B of 1b. The conductive portion 72A of 1a is arranged on the surface of the base particle 2. The conductive portion 72B of 1b is arranged on the surface of the conductive portion 72A of 1a. The conductive portion 72A of 1a and the conductive portion 72B of 1b are arranged between the base particle 2 and the second conductive portion (solder portion) 72C. The conductive portion 72A of 1a is in contact with the base particle 2. The second conductive portion (solder portion) 72C is in contact with the conductive portion 72B of 1b. Therefore, the conductive portion 72A of 1a is disposed on the surface of the base particle 2, the conductive portion 72B of 1b is disposed on the surface of the conductive portion 72A of 1a, and the second conductive portion (solder portion) 72C is disposed on the surface of the conductive portion 72B of 1b. In the conductive particle, the base particle may be completely covered by the conductive portion of 1a and the conductive portion of 1b, or may not be completely covered. The base particle may have a portion that is not covered by the conductive portion of 1a and the conductive portion of 1b. The conductive portion of 1a, the conductive portion of 1b, and the second conductive portion (solder portion) may be formed as different conductive portions, or may be formed as the same conductive portion. The second conductive portion (solder portion) is formed of solder. The second conductive portion (solder portion) is preferably a solder grain described later. In the conductive particle, it is preferable that the conductive portion 1a is arranged on the surface of the base particle, the conductive portion 1b is arranged on the surface of the conductive portion 1a, and the solder grains are arranged on the surface of the conductive portion 1b.
[0093] A metal film 73 is disposed on the surface of the conductive portion 72. The metal film may be disposed only on the surface of the conductive portion 1b, may be disposed only on the surface of the second conductive portion (solder portion), or may be disposed on the surfaces of the conductive portion 1b and the second conductive portion (solder portion). The metal film is preferably disposed only on the surface of the second conductive portion (solder portion), and is preferably disposed only on the surface of the solder grain. In the conductive particle, the conductive portion may be completely covered by the metal film, or may not be completely covered. The conductive portion may have a portion that is not covered by the metal film.
[0094] In the conductive particle 71, the conductive portion 72 includes a component capable of metal diffusion at 400° C. or less, or the conductive portion 72 is melt-deformable at 400° C. or less. The conductive portion 72 may include a component capable of metal diffusion at 400° C. or less, or the conductive portion 72 may be melt-deformable at 400° C. or less. The conductive portion 72 may include a component capable of metal diffusion at 400° C. or less, and the conductive portion 72 may be melt-deformable at 400° C. or less. In the conductive particle 71, the second conductive portion 72C (solder portion) is a component capable of metal diffusion at 400° C. or less. In the conductive particle 71, the second conductive portion 72C (solder portion) is melt-deformable at 400° C. or less. In the conductive particle, the conductive portion 1a or the conductive portion 1b may be a component capable of metal diffusion at 400° C. or less, or the conductive portion 1a or the conductive portion 1b may be melt-deformable at 400° C. or less. In the above conductive particles, the conductive portion 1a, the conductive portion 1b and the second conductive portion (solder portion) may be components capable of metal diffusion at 400°C or less, and the conductive portion 1a, the conductive portion 1b and the second conductive portion (solder portion) may be melt-deformable at 400°C or less.
[0095] Other details of the conductive particles will be described below. In the following description, "(meth)acrylic" means either or both of "acrylic" and "methacrylic", "(meth)acryloxy" means either or both of "acryloxy" and "methacryloxy", and "(meth)acrylate" means either or both of "acrylate" and "methacrylate".
[0096] (base material particles) The material of the base particle is not particularly limited. The material of the base particle may be an organic material or an inorganic material. Examples of the base particle formed only from the organic material include resin particles. Examples of the base particle formed only from the inorganic material include inorganic particles other than metals. Examples of the base particle formed from both the organic material and the inorganic material include organic-inorganic hybrid particles. From the viewpoint of further improving the compression characteristics of the base particle, the base particle is preferably a resin particle or an organic-inorganic hybrid particle, and more preferably a resin particle.
[0097] Examples of the organic material include polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyether ether ketone, polyether sulfone, divinylbenzene polymer, and divinylbenzene copolymer. Examples of the divinylbenzene copolymer include divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylic acid ester copolymer. The material of the base particle is preferably a polymer obtained by polymerizing one or more polymerizable monomers having an ethylenically unsaturated group, since the compression characteristics of the base particle can be easily controlled within a suitable range.
[0098] When the base particle is obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, the polymerizable monomer having an ethylenically unsaturated group includes a non-crosslinkable monomer and a crosslinkable monomer.
[0099] Examples of the non-crosslinkable monomer include vinyl compounds such as styrene monomers, α-methylstyrene, and chlorostyrene; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; halogen-containing monomers such as vinyl chloride and vinyl fluoride; and (meth)acrylic compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl Examples of suitable (meth)acrylate compounds include alkyl (meth)acrylate compounds such as (meth)acrylate and isobornyl (meth)acrylate; oxygen-containing (meth)acrylate compounds such as 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; halogen-containing (meth)acrylate compounds such as trifluoromethyl (meth)acrylate and pentafluoroethyl (meth)acrylate; α-olefin compounds such as diisobutylene, isobutylene, linearne, ethylene, and propylene; and conjugated diene compounds such as isoprene and butadiene.
[0100] Examples of the crosslinkable monomer include vinyl compounds such as vinyl monomers, e.g., divinylbenzene, 1,4-divinyloxybutane, and divinylsulfone; (meth)acrylic compounds such as polyfunctional (meth)acrylate compounds, e.g., tetramethylolmethane tetra(meth)acrylate, polytetramethylene glycol diacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; and allyl compounds. Examples of the silane compounds include silane alkoxide compounds such as tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, isopropyltrimethoxysilane, isobutyltrimethoxysilane, cyclohexyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, 1,3-divinyltetramethyldisiloxane, methylphenyldimethoxysilane, and diphenyldimethoxysilane;Examples of the silane alkoxides include silanes containing polymerizable double bonds, such as vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, dimethoxyethylvinylsilane, diethoxymethylvinylsilane, diethoxyethylvinylsilane, ethylmethyldivinylsilane, methylvinyldimethoxysilane, ethylvinyldimethoxysilane, methylvinyldiethoxysilane, ethylvinyldiethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane; cyclic siloxanes such as decamethylcyclopentasiloxane; modified (reactive) silicone oils such as one-end modified silicone oil, both-end silicone oil, and side-chain silicone oil; and carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride.
[0101] Examples of the inorganic material include silica, alumina, barium titanate, zirconia, carbon black, silicate glass, borosilicate glass, lead glass, soda-lime glass, and alumina silicate glass.
[0102] The base particle may be an organic-inorganic hybrid particle. The base particle may be a core-shell particle. When the base particle is an organic-inorganic hybrid particle, examples of the inorganic material of the base particle include silica, alumina, barium titanate, zirconia, and carbon black. The inorganic material is preferably not a metal. The base particle formed of silica is not particularly limited, but examples include base particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form crosslinked polymer particles, and then baking the resulting particles as necessary. The organic-inorganic hybrid particle may be an organic-inorganic hybrid particle formed of a crosslinked alkoxysilyl polymer and an acrylic resin.
[0103] The organic-inorganic hybrid particles are preferably core-shell type organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. The base particle is preferably an organic-inorganic hybrid particle having an organic core and an inorganic shell disposed on the surface of the organic core.
[0104] Examples of the material for the organic core include the organic materials described above.
[0105] The material of the inorganic shell may be any of the inorganic substances listed as the material of the base particle. The material of the inorganic shell is preferably silica. The inorganic shell is preferably formed by forming a shell-like material from a metal alkoxide on the surface of the core by a sol-gel method, and then firing the shell-like material. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed from a silane alkoxide.
[0106] The particle diameter of the base particle is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle diameter of the base particle is the above lower limit or more and the above upper limit or less, it can be used more suitably to obtain conductive particles. When the particle diameter of the base particle is the above lower limit or more and the above upper limit or less, the contact area between the conductive particle and the electrode can be sufficiently large, and when forming the conductive part, aggregated conductive particles are unlikely to be formed, and the conductive part is unlikely to peel off from the surface of the base particle.
[0107] The particle diameter of the base particle is particularly preferably 1 μm or more and 50 μm or less. When the particle diameter of the base particle is within the range of 1 μm or more and 50 μm or less, it is difficult to aggregate when forming a conductive part on the surface of the base particle, and it is difficult to form aggregated conductive particles. In addition, when the particle diameter of the base particle is within the range of 1 μm or more and 50 μm or less, it can be used more preferably to obtain conductive particles.
[0108] The particle size of the base particle refers to the diameter when the base particle is a perfect sphere, and when the base particle is not a perfect sphere, it refers to the diameter when the base particle is assumed to be a perfect sphere of equivalent volume.
[0109] The particle diameter of the base particle indicates the number average particle diameter. The particle diameter of the base particle is obtained by observing 50 arbitrary base particles with an electron microscope or optical microscope and calculating the average particle diameter of each base particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or optical microscope, the particle diameter of each base particle is obtained as the particle diameter of a circle equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle diameter of 50 arbitrary base particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each base particle is obtained as the particle diameter of a sphere equivalent diameter. The average particle diameter of the base particles is preferably calculated using a particle size distribution measuring device. When the particle diameter of the base particles in the conductive particles is measured, it can be measured, for example, as follows.
[0110] The conductive particles are added to Kulzer's Technovit 4000 so that the content of the conductive particles is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the conductive particles dispersed in the resin body for inspection. Then, 50 conductive particles are randomly selected using a field emission scanning electron microscope (FE-SEM), and the base particle of each conductive particle is observed. The particle diameter of the base particle in each conductive particle is measured, and the arithmetic average of the measured particle diameters is determined as the particle diameter of the base particle.
[0111] (Conductive part) The conductive particle according to the present invention includes a base particle and a conductive portion disposed on a surface of the base particle. The conductive portion preferably contains a metal.
[0112] In the conductive particles, the conductive part contains a component capable of metal diffusion at 400° C. or less, or the conductive part is meltable and deformable at 400° C. or less. By lowering the temperature at which metal diffusion can occur, a metal bond can be more easily formed with a joint part such as an electrode. Therefore, the temperature at which metal diffusion can occur is preferably 350° C. or less, more preferably 300° C. or less, even more preferably 250° C. or less, and particularly preferably 200° C. or less. The temperature at which metal diffusion can occur can be controlled by the type of metal.
[0113] In addition, the conductive part is preferably melt-deformable at 400°C or less. The conductive part is preferably melt-deformable at 350°C or less, more preferably melt-deformable at 300°C or less, even more preferably melt-deformable at 250°C or less, and particularly preferably melt-deformable at 200°C or less. When the melt-deformation temperature of the conductive part is in the above-mentioned preferred range, the melt-deformation temperature can be lowered, the amount of energy consumed during heating can be reduced, and thermal deterioration of the connection target member and the like can be suppressed. The melt-deformation temperature of the conductive part can be controlled by the type of metal of the conductive part. The conductive part may have a part exceeding 200°C, a part exceeding 250°C, a part exceeding 300°C, a part exceeding 350°C, or a part exceeding 400°C.
[0114] The metal constituting the conductive part is not particularly limited. Examples of the metal constituting the conductive part include gold, silver, palladium, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum, and alloys thereof. Examples of the metal constituting the conductive part include tin-doped indium oxide (ITO) and solder. Only one type of metal may be used as the metal constituting the conductive part, or two or more types may be used in combination.
[0115] In the present invention, the metal constituting the conductive part is preferably selected so that the conductive part contains a component capable of metal diffusion at 400° C. or less and is melt deformable at 400° C. or less. The conductive part preferably contains solder and preferably has a solder part. The solder part is formed of solder. The conductive part preferably has a solder part formed of solder.
[0116] From the viewpoint of more effectively reducing the connection resistance, the conductive portion preferably contains nickel, gold, palladium, silver, copper, tin or an alloy containing tin, and more preferably contains nickel, gold, palladium, tin or an alloy containing tin.
[0117] In 100% by weight of the conductive part containing silver, the silver content is preferably 0.1% by weight or more, more preferably 1% by weight or more, and preferably 100% by weight or less, more preferably 90% by weight or less. The silver content may be 80% by weight or less, 60% by weight or less, 40% by weight or less, 20% by weight or less, or 10% by weight or less. When the silver content is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of aggregation between conductive particles can be more effectively suppressed.
[0118] In 100% by weight of the copper-containing conductive part, the copper content is preferably 0.1% by weight or more, more preferably 1% by weight or more, and preferably 100% by weight or less, more preferably 90% by weight or less. The copper content may be 80% by weight or less, 60% by weight or less, 40% by weight or less, 20% by weight or less, or 10% by weight or less. When the copper content is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of aggregation between the conductive particles can be more effectively suppressed.
[0119] In 100% by weight of the conductive part containing tin or an alloy containing tin, the content of tin or an alloy containing tin is preferably 20% by weight or more, more preferably 50% by weight or more, and particularly preferably 90% by weight or more. When the content of the tin or the alloy containing tin is equal to or more than the lower limit, the occurrence of aggregation between the conductive particles can be more effectively suppressed.
[0120] The solder is preferably a metal having a melting point of 450°C or less (low melting point metal). The low melting point metal refers to a metal having a melting point of 450°C or less. The melting point of the low melting point metal is preferably 300°C or less, more preferably 160°C or less. The solder also contains tin. In 100% by weight of the metal contained in the solder, the tin content is preferably 30% by weight or more, more preferably 40% by weight or more, even more preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the tin content in the solder is equal to or more than the lower limit, the electrical conductivity reliability is further increased.
[0121] The contents of nickel, copper, and tin can be measured using a high-frequency inductively coupled plasma atomic emission spectrometer ("ICP-AES" manufactured by Horiba, Ltd.) or a fluorescent X-ray analyzer ("EDX-800HS" manufactured by Shimadzu Corporation).
[0122] By using the solder, the solder melts and bonds to the electrodes, and the solder conducts electricity between the electrodes. For example, the solder and the electrodes are easily in surface contact rather than in point contact, so that the connection resistance is low. In addition, the use of solder increases the bonding strength between the solder and the electrodes, so that the solder and the electrodes are less likely to peel off, and the reliability of the electrical connection is more effectively increased.
[0123] The low melting point metal constituting the solder is not particularly limited. The low melting point metal is preferably tin or an alloy containing tin. Examples of the alloy include a tin-silver alloy, a tin-copper alloy, a tin-silver-copper alloy, a tin-bismuth alloy, a tin-zinc alloy, and a tin-indium alloy. Since the low melting point metal has excellent wettability with respect to the electrode, it is preferable that the low melting point metal is tin, a tin-silver alloy, a tin-silver-copper alloy, a tin-bismuth alloy, or a tin-indium alloy, and more preferably a tin-bismuth alloy or a tin-indium alloy.
[0124] The solder is preferably a filler metal having a liquidus of 450°C or less based on JIS Z3001: Welding Terminology. Examples of the composition of the solder include metal compositions containing zinc, gold, silver, lead, copper, tin, bismuth, indium, etc. The solder is preferably a tin-indium type (117°C eutectic) or a tin-bismuth type (139°C eutectic) that has a low melting point and is lead-free. That is, the solder is preferably lead-free and contains tin and indium, or tin and bismuth.
[0125] In order to further increase the bonding strength, the solder may contain metals such as nickel, copper, antimony, aluminum, zinc, iron, gold, titanium, phosphorus, germanium, tellurium, cobalt, bismuth, manganese, chromium, molybdenum, palladium, etc. From the viewpoint of further increasing the bonding strength, it is more preferable that the solder contains nickel, copper, antimony, aluminum, or zinc. From the viewpoint of further increasing the bonding strength, the content of these metals for increasing the bonding strength is preferably 0.0001% by weight or more, and preferably 1% by weight or less, in 100% by weight of the solder.
[0126] The conductive portion may be formed of one layer. The conductive portion may be formed of multiple layers. That is, the conductive portion may have a laminated structure of two or more layers. From the viewpoint of more effectively increasing the conduction reliability, it is preferable that the conductive portion has a laminated structure of two or more layers.
[0127] The method for forming the conductive portion on the surface of the base particle is not particularly limited. Examples of the method for forming the conductive portion include the following methods. A method using electroless plating. A method using electroplating. A method using physical collision. A method using mechanochemical reaction. A method using physical vapor deposition or physical adsorption. A method of coating the surface of the base particle with a metal powder or a paste containing a metal powder and a binder. The method for forming the conductive portion is preferably electroless plating, electroplating, or a method using physical collision. Examples of the method using physical vapor deposition include vacuum deposition, ion plating, and ion sputtering. Also, as the method using physical collision, a sheeter composer (manufactured by Tokuju Machine Works) or the like is used.
[0128] The thickness of the conductive part is preferably 10 nm or more, more preferably 500 nm or more, and preferably 10 μm or less, more preferably 5 μm or less, even more preferably 1 μm or less, and particularly preferably 800 nm or less. The thickness of the conductive part means the thickness of the entire conductive part when the conductive part has a laminated structure of two or more layers. When the thickness of the conductive part is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of aggregation of the conductive particles can be more effectively suppressed. Furthermore, when the thickness of the conductive part is equal to or more than the lower limit and equal to or less than the upper limit, sufficient conductivity can be obtained and the conductive particles can be prevented from becoming hard.
[0129] When the conductive portion has a laminated structure of two or more layers, the thickness of the conductive portion of the outermost layer is preferably 10 nm or more, more preferably 500 nm or more, and preferably 10 μm or less, more preferably 5 μm or less, even more preferably 1 μm or less, and particularly preferably 800 nm or less. When the thickness of the conductive portion of the outermost layer is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of aggregation of the conductive particles can be more effectively suppressed.
[0130] The thickness of the conductive part can be measured by observing the cross section of the conductive particle using, for example, a transmission electron microscope (TEM). The thickness of the conductive part is preferably the thickness of the part where the conductive part is the thickest in any conductive particle. The thickness of the conductive part is preferably determined by calculating the average thickness of the conductive part of 10 arbitrary conductive particles.
[0131] Solder Grain: In the conductive particle, the conductive portion has a solder portion. The conductive portion has a solder portion formed by solder.
[0132] From the viewpoint of more effectively suppressing the occurrence of aggregation between the conductive particles, the solder part is preferably a solder grain. In the conductive particles, the conductive part preferably has a solder grain. For example, the second conductive part (solder part) 3B in FIG. 1, the second conductive part (solder part) 12C in FIG. 2, the second conductive part (solder part) 22B in FIG. 3, and the second conductive part (solder part) 32B in FIG. 4 are preferably solder grains. In addition, the second conductive part (solder part) 42B in FIG. 5, the second conductive part (solder part) 52C in FIG. 6, the second conductive part (solder part) 62B in FIG. 7, and the second conductive part (solder part) 72C in FIG. 8 are preferably solder grains.
[0133] The solder grains are different from the protrusions described later. The solder grains can form a metallic bond with a joint portion of an electrode or the like. The solder grains are used for joining with an electrode or the like. Since the conductive portion has the solder grains, the solder grains can easily form a metallic bond with a joint portion of an electrode or the like, so there is no need to melt the entire conductive portion during joining. As a result, even if the conductive portion is relatively thin, the reliability of conduction between the electrodes can be improved. Furthermore, since there is no need to increase the thickness of the conductive portion, agglomeration of the conductive particles can be effectively suppressed.
[0134] In addition, since the solder particles are relatively small, the outer surfaces of the solder particles are relatively resistant to oxidation, and the effect of the oxide film can be suppressed. Therefore, the solder particles can more easily form a metallic bond with the joint parts such as electrodes. On the other hand, when the conductive particles are not the solder particles but have a solder layer covered with solder, the outer surface of the solder layer is relatively resistant to oxidation, and it is difficult to suppress the effect of the oxide film. Therefore, the solder layer cannot easily form a metallic bond with the joint parts such as electrodes, and measures such as thickening the solder layer are required, making it difficult to suppress the occurrence of aggregation of the conductive particles.
[0135] The shape of the solder grains is not particularly limited. The shape of the solder grains is preferably a needle shape or a part of a sphere shape. The needle shape is preferably a pyramidal shape, a conical shape, or a paraboloid of revolution, more preferably a conical shape or a paraboloid of revolution, and even more preferably a conical shape. The shape of the solder grains may be a pyramidal shape, a conical shape, or a paraboloid of revolution.
[0136] The material of the solder grains is not particularly limited. The solder grains are preferably made of metal. The material of the solder grains preferably includes an alloy containing tin, is pure tin, or contains tin in a state different from that of an alloy containing tin and different from that of pure tin. The material of the solder grains may include an alloy containing tin or may be pure tin. The material of the solder grains may be an alloy containing tin or may be pure tin. The material of the solder grains may contain tin in a state different from that of an alloy containing tin and different from that of pure tin. From the viewpoint of more effectively suppressing the occurrence of aggregation between conductive particles, it is more preferable that the material of the solder grains is pure tin. The material of the solder grains being pure tin means that the tin content is 90% by weight or more in 100% by weight of the material of the solder grains. The tin content may be less than 90% by weight, 80% by weight or less, 75% by weight or less, or 70% by weight or less in 100% by weight of the material of the solder grains.
[0137] In 100% by weight of the solder particles containing tin, the tin content is preferably 20% by weight or more, more preferably 40% by weight or more, even more preferably 90% by weight or more, and preferably 99.5% by weight or less, more preferably 99% by weight or less. When the tin content is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the tin content is equal to or more than the lower limit and equal to or less than the upper limit, the solder particles can more easily form a metallic bond with the joining portion of the electrode or the like.
[0138] The height of the solder particles is preferably 10 nm or more, more preferably 250 nm or more, even more preferably 350 nm or more, particularly preferably 500 nm or more, and preferably 10 μm or less, more preferably 5 μm or less. When the height of the solder particles is equal to or greater than the lower limit and equal to or less than the upper limit, the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the height of the solder particles is equal to or greater than the lower limit and equal to or less than the upper limit, the solder particles can more easily form a metallic bond with the joining portion of the electrode or the like, and a conductive characteristic superior to physical contact can be obtained, and the joining strength can be further increased.
[0139] The height of the solder grains indicates the distance from the outer surface of the first conductive part to the tip of the solder grain (solder part) on the line (dashed line L1 shown in Figure 1) connecting the center of the conductive particle and the tip of the solder grain (solder part) when it is assumed that the solder grain (solder part) is not present. That is, in Figure 1, it indicates the distance from the intersection L2 between the dashed line L1 and the outer surface of the first conductive part to the tip of the solder grain (solder part). The height of the solder grains is preferably the average height of the solder grains in one conductive particle. The height of the solder grains is preferably the average height of the solder grains at five points on the conductive particle.
[0140] The height of the solder particles can be measured, for example, as follows.
[0141] The conductive particles are added to Kulzer's Technovit 4000 so that the content of the conductive particles is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the conductive particles dispersed in the resin body for inspection. Then, a field emission scanning electron microscope (FE-SEM) is used to randomly select conductive particles and observe the solder particles in the conductive particles. The heights of the solder particles at five points in the conductive particle are measured, and the arithmetic average of these measurements is determined as the height of the solder particles.
[0142] The aspect ratio of the solder particles is preferably 0.05 or more, more preferably 0.47 or more, even more preferably 0.5 or more, and is preferably 5 or less, more preferably 3 or less. When the aspect ratio of the solder particles is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the aspect ratio of the solder particles is equal to or more than the lower limit and equal to or less than the upper limit, the solder particles can more easily form metallic bonds with the joints of electrodes, etc., and a sufficient area can be secured between the solder particles and the joints of electrodes, etc.
[0143] The aspect ratio of the solder grain is the ratio of the height of the solder grain to the width of the solder grain (height of solder grain / width of solder grain), and is calculated from the height and width of the solder grain. As described above, the height of the solder grain indicates the distance from the outer surface of the first conductive part to the tip of the solder grain (solder part) on the line (dashed line L1 shown in FIG. 1) connecting the center of the conductive particle and the tip of the solder grain (solder part) when it is assumed that the solder grain (solder part) does not exist. The width of the solder grain indicates the maximum distance of a straight line connecting two points on the periphery of the solder grain (solder part) in a direction perpendicular to the line connecting the center of the conductive particle and the tip of the solder grain (solder part). The width of the solder grain is preferably the average width of the solder grain in one conductive particle. The width of the solder grain is preferably the average width of the solder grain at five points in the conductive particle.
[0144] The width of the solder grain can be measured, for example, as follows.
[0145] The conductive particles are added to Kulzer's Technovit 4000 so that the content of the conductive particles is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the conductive particles dispersed in the resin body for inspection. Then, a field emission scanning electron microscope (FE-SEM) is used to randomly select conductive particles and observe the solder grains in the conductive particles. The widths of the solder grains at five points in the conductive particle are measured, and the arithmetic average of these measurements is used to determine the width of the solder grain.
[0146] The width of the solder grains is preferably 250 nm or more, more preferably 500 nm or more, and even more preferably 650 nm or more, and is preferably 3000 nm or less, more preferably 1700 nm or less, and even more preferably 1500 nm or less. When the width of the solder grains is equal to or greater than the lower limit and equal to or less than the upper limit, the occurrence of aggregation between the conductive particles can be more effectively suppressed. When the width of the solder grains is equal to or greater than the lower limit and equal to or less than the upper limit, the solder grains can more easily form a metallic bond with the joining portion of the electrodes, etc., and a conductive characteristic superior to physical contact can be obtained, and the joining strength can be further increased.
[0147] The method for forming the solder particles is not particularly limited. Examples of the method for forming the solder particles include electroless plating and electroplating. In the present invention, not only a film-like shape but also a granular shape is considered to be plating.
[0148] The conductive particles preferably have a metal colloid deposit or a metal film on the outer surface of the solder grain. The conductive particles may have a metal colloid deposit or a metal film on the outer surface of the solder grain.
[0149] When the conductive particles satisfy the above-mentioned preferred aspects, it is possible to change the melting point or metal diffusion temperature of the solder grains (the solder portion) and the conductive portion, and to set the temperature to a more suitable temperature for the joint portion of the electrodes, etc. As a result, it is possible for the solder grains to more easily form a metallic bond with the joint portion of the electrodes, etc.
[0150] Of the total surface area of the solder grains (100%), the area of the portion where the metal colloid deposit or metal film is present (the coverage of the metal colloid deposit or metal film) is preferably 5% or more, more preferably 40% or more, and preferably 100% or less, more preferably 95% or less. When the coverage (the coverage of the metal colloid deposit or metal film) is equal to or more than the lower limit and equal to or less than the upper limit, the melting point or metal diffusion temperature of the solder grains (the solder portion) and the conductive portion can be changed, and a temperature more suitable for the joint portion of the electrodes, etc. can be obtained. As a result, the solder grains can more easily form metallic bonds with the joint portions of the electrodes, etc.
[0151] The area of the portion where the metal colloid deposit or the metal film is present (the coverage rate of the metal colloid deposit or the metal film) out of the total surface area of the solder particle (100%) can be calculated by performing elemental mapping by SEM-EDX analysis of the cross section of the solder particle in the conductive particle and performing image analysis.
[0152] The metal species of the metal colloid deposit or the metal species of the metal film are preferably nickel, cobalt, lead, gold, zinc, palladium, copper, silver, bismuth, or indium, and more preferably copper, silver, bismuth, or indium. When the metal species of the metal colloid deposit or the metal species of the metal film satisfy the above-mentioned preferred aspects, the melting point or metal diffusion temperature of the solder grains (the solder portion) and the conductive portion can be changed, and the temperature can be made more suitable for the joint portion of the electrodes, etc. As a result, the solder grains can more easily form a metallic bond with the joint portion of the electrodes, etc.
[0153] The metal colloid for obtaining the metal colloid precipitate is preferably a nickel colloid, a cobalt colloid, a lead colloid, a gold colloid, a zinc colloid, a palladium colloid, a copper colloid, a silver colloid, a bismuth colloid, or an indium colloid. The metal colloid for obtaining the metal colloid precipitate is more preferably a copper colloid, a silver colloid, a bismuth colloid, or an indium colloid. The metal film is preferably a nickel thin film, a cobalt thin film, a lead thin film, a gold thin film, a zinc thin film, a palladium thin film, a copper thin film, a silver thin film, a bismuth thin film, or an indium thin film. The metal film is more preferably a copper thin film, a silver thin film, a bismuth thin film, or an indium thin film. When the metal colloid precipitate or the metal film satisfies the above preferred aspects, the melting point or metal diffusion temperature of the solder grain (the solder portion) and the conductive portion can be changed, and the temperature can be made more suitable for the joint portion of the electrode or the like. As a result, the solder grain can more easily form a metal bond with the joint portion of the electrode or the like.
[0154] The metal colloid precipitate is preferably metal fine particles. The particle diameter of the metal fine particles is preferably 1 nm or more, more preferably 10 nm or more, and preferably 1 μm or less, more preferably 0.5 μm or less. The thickness of the metal film is preferably 1 nm or more, more preferably 10 nm or more, and preferably 1 μm or less, more preferably 0.5 μm or less. When the particle diameter of the metal fine particles or the thickness of the metal film satisfies the above-mentioned preferred embodiment, the melting point or metal diffusion temperature of the solder grains (the solder portion) and the conductive portion can be changed, and the temperature can be made more suitable for the joint portion of the electrodes, etc. As a result, the solder grains can more easily form a metal bond with the joint portion of the electrodes, etc.
[0155] The particle size of the metal colloid precipitate or the thickness of the metal film can be measured, for example, as follows.
[0156] The conductive particles are added to Kulzer's Technovit 4000 so that the content of the conductive particles is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the conductive particles dispersed in the resin body for inspection. Then, a field emission scanning electron microscope (FE-SEM) is used to randomly select conductive particles and observe the metal colloid deposits or metal film in the solder grains. The particle diameters of the metal colloid deposits or the thicknesses of the metal film are measured at five points in the solder grains, and the arithmetic average of these is determined to be the particle diameters of the metal colloid deposits or the thickness of the metal film.
[0157] The method for disposing the metal colloid deposit or metal film on the outer surface of the solder particle is not particularly limited, and examples of the method for disposing the metal colloid deposit or metal film on the outer surface of the solder particle include an electroless plating method, an electroplating method, a physical collision method, and a physical vapor deposition or physical adsorption method.
[0158] (core substance) The conductive particles preferably have protrusions on the outer surface of the conductive part. The conductive particles preferably have protrusions on the conductive surface. The protrusions are preferably multiple. An oxide film is often formed on the surface of the electrode that contacts the conductive particles. When conductive particles having protrusions on the surface of the conductive part are used, the oxide film can be effectively removed by the protrusions by pressing the conductive particles and the electrode. Therefore, the electrode and the conductive part are more reliably in contact with each other, the contact area between the conductive particles and the electrode can be sufficiently increased, and the connection resistance can be more effectively reduced. Furthermore, when the conductive particles are dispersed in a binder and used as a conductive material, the binder between the conductive particles and the electrode can be more effectively removed by the protrusions of the conductive particles. Therefore, the contact area between the conductive particles and the electrode can be sufficiently increased, and the connection resistance can be more effectively reduced.
[0159] The protrusions are different from the solder grains described above. The protrusions are used to remove the oxide film present on the surfaces of the conductive particles and electrodes, and to remove the binder between the conductive particles and the electrodes.
[0160] Examples of the method for forming the protrusions include a method in which a core material is attached to the surface of a base particle, and then a conductive portion is formed by electroless plating, and a method in which a conductive portion is formed on the surface of a base particle by electroless plating, and then a core material is attached, and then a conductive portion is formed by electroless plating, etc. Also, the core material does not have to be used to form the protrusions.
[0161] Other methods for forming the protrusions include a method of adding a core substance during the process of forming a conductive portion on the surface of a base particle, etc. Alternatively, to form the protrusions, a method may be used in which, without using the core substance, a conductive portion is formed on the base particle by electroless plating, a plating is deposited in the form of protrusions on the surface of the conductive portion, and the conductive portion is further formed by electroless plating, etc.
[0162] Examples of the method for attaching the core substance to the surface of the base particle include a method of adding the core substance to a dispersion liquid of the base particle, and accumulating and attaching the core substance to the surface of the base particle by van der Waals force, and a method of adding the core substance to a container containing the base particle, and attaching the core substance to the surface of the base particle by mechanical action such as rotating the container, etc. From the viewpoint of controlling the amount of the core substance to be attached, the method for attaching the core substance to the surface of the base particle is preferably a method of accumulating and attaching the core substance to the surface of the base particle in the dispersion liquid.
[0163] The materials constituting the core material include conductive materials and non-conductive materials. The conductive materials include conductive non-metals such as metals, metal oxides, and graphite, and conductive polymers. The conductive polymers include polyacetylene. The non-conductive materials include silica, alumina, and zirconia. From the viewpoint of more effectively removing the oxide film, it is preferable that the core material is hard. From the viewpoint of more effectively lowering the connection resistance between the electrodes, it is preferable that the core material is a metal.
[0164] The metal is not particularly limited. Examples of the metal include gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium, and cadmium, as well as alloys consisting of two or more metals, such as tin-lead alloy, tin-copper alloy, tin-silver alloy, tin-lead-silver alloy, and tungsten carbide. From the viewpoint of more effectively lowering the connection resistance between the electrodes, the metal is preferably nickel, copper, silver, or gold. The metal may be the same as or different from the metal constituting the conductive portion (conductive layer).
[0165] The shape of the core material is not particularly limited. The core material is preferably in the form of a lump. Examples of the core material include a particulate lump, an aggregate of a plurality of microparticles, and an amorphous lump.
[0166] The particle size of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, and preferably 0.9 μm or less, more preferably 0.2 μm or less. When the particle size of the core material is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced.
[0167] The particle diameter of the core material is preferably an average particle diameter, and more preferably a number average particle diameter. The particle diameter of the core material is determined by observing 50 arbitrary core materials with an electron microscope or optical microscope and calculating the average particle diameter of each core material, or by using a particle size distribution measuring device. In the observation with an electron microscope or optical microscope, the particle diameter of each core material is determined as the particle diameter of a circle equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle diameter of 50 arbitrary core materials with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each core material is determined as the particle diameter of a sphere equivalent diameter. The average particle diameter of the core material is preferably calculated using a particle size distribution measuring device.
[0168] The number of the protrusions per conductive particle is preferably 3 or more, more preferably 5 or more. The upper limit of the number of the protrusions is not particularly limited. The upper limit of the number of the protrusions can be appropriately selected in consideration of the particle diameter of the conductive particles. When the number of the protrusions is equal to or more than the lower limit, the connection resistance between the electrodes can be more effectively reduced.
[0169] The number of protrusions can be calculated by observing any conductive particle with an electron microscope or an optical microscope. The number of protrusions is preferably determined by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average number of protrusions on each conductive particle.
[0170] The height of the protrusions is preferably 0.001 μm or more, more preferably 0.05 μm or more, and is preferably 0.9 μm or less, more preferably 0.2 μm or less. When the height of the protrusions is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be reduced more effectively.
[0171] The height of the protrusions can be calculated by observing the protrusions of any conductive particle with an electron microscope or an optical microscope. The height of the protrusions is preferably calculated by taking the average value of the heights of all the protrusions per conductive particle as the height of the protrusions of one conductive particle. The height of the protrusions is preferably determined by calculating the average value of the heights of the protrusions of 50 arbitrary conductive particles.
[0172] (Insulating material) The conductive particles preferably have an insulating material disposed on the outer surface of the conductive portion. In this case, when the conductive particles are used for connecting electrodes, short-circuiting between adjacent electrodes can be prevented more effectively. Specifically, when a plurality of conductive particles contact each other, an insulating material exists between the plurality of electrodes, so that short-circuiting between adjacent electrodes in the horizontal direction, rather than between upper and lower electrodes, can be prevented. In addition, when connecting electrodes, the insulating material between the conductive portion of the conductive particles and the electrodes can be easily removed by pressing the conductive particles with two electrodes. Furthermore, when the conductive particles have protrusions on the outer surface of the conductive portion, the insulating material between the conductive portion of the conductive particles and the electrodes can be more easily removed.
[0173] The insulating material is preferably insulating particles, since this allows the insulating material to be removed more easily when the electrodes are pressed together.
[0174] Examples of the material of the insulating substance include the above-mentioned organic materials, the above-mentioned inorganic materials, and the above-mentioned inorganic substances as the materials of the base particle, etc. The material of the insulating substance is preferably the above-mentioned organic material.
[0175] Other materials for the insulating material include polyolefin compounds, (meth)acrylate polymers, (meth)acrylate copolymers, block polymers, thermoplastic resins, crosslinked products of thermoplastic resins, thermosetting resins, water-soluble resins, etc. Only one type of the insulating material may be used, or two or more types may be used in combination.
[0176] Examples of the polyolefin compound include polyethylene, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid ester copolymer. Examples of the (meth)acrylate polymer include polymethyl (meth)acrylate, polydodecyl (meth)acrylate, and polystearyl (meth)acrylate. Examples of the block polymer include polystyrene, styrene-acrylic acid ester copolymer, SB type styrene-butadiene block copolymer, SBS type styrene-butadiene block copolymer, and hydrogenated products thereof. Examples of the thermoplastic resin include vinyl polymers and vinyl copolymers. Examples of the thermosetting resin include epoxy resin, phenolic resin, and melamine resin. Examples of the crosslinked thermoplastic resin include the introduction of polyethylene glycol methacrylate, alkoxylated trimethylolpropane methacrylate, and alkoxylated pentaerythritol methacrylate. Examples of the water-soluble resin include polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyvinylpyrrolidone, polyethylene oxide, and methyl cellulose. In addition, a chain transfer agent may be used to adjust the degree of polymerization. Examples of the chain transfer agent include thiol and carbon tetrachloride.
[0177] The method of disposing the insulating material on the surface of the conductive part includes a chemical method, and a physical or mechanical method. The chemical method includes an interfacial polymerization method, a suspension polymerization method in the presence of particles, and an emulsion polymerization method. The physical or mechanical method includes a spray drying method, a hybridization method, an electrostatic adhesion method, a spraying method, a dipping method, and a vacuum deposition method. From the viewpoint of more effectively increasing the insulation reliability and the conduction reliability when the electrodes are electrically connected, the method of disposing the insulating material on the surface of the conductive part is preferably a physical method.
[0178] The outer surface of the conductive part and the outer surface of the insulating material may each be coated with a compound having a reactive functional group. The outer surface of the conductive part and the outer surface of the insulating material may not be directly chemically bonded, and may be indirectly chemically bonded by a compound having a reactive functional group. After a carboxyl group is introduced onto the outer surface of the conductive part, the carboxyl group may be chemically bonded to a functional group on the outer surface of the insulating material via a polymer electrolyte such as polyethyleneimine.
[0179] When the insulating material is an insulating particle, the particle diameter of the insulating particle can be appropriately selected depending on the particle diameter of the conductive particle and the use of the conductive particle. The particle diameter of the insulating particle is preferably 10 nm or more, more preferably 100 nm or more, even more preferably 300 nm or more, particularly preferably 500 nm or more, and preferably 4000 nm or less, more preferably 2000 nm or less, even more preferably 1500 nm or less, particularly preferably 1000 nm or less. If the particle diameter of the insulating particle is above the lower limit, when the conductive particle is dispersed in the binder, the conductive parts of the multiple conductive particles are less likely to contact each other. If the particle diameter of the insulating particle is below the upper limit, it is not necessary to apply too much pressure or heat to a high temperature in order to remove the insulating particles between the electrodes and the conductive particles when connecting the electrodes.
[0180] The particle diameter of the insulating particles is preferably an average particle diameter, and is preferably a number average particle diameter. The particle diameter of the insulating particles is obtained by observing 50 arbitrary insulating particles with an electron microscope or an optical microscope and calculating the average particle diameter of each insulating particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or an optical microscope, the particle diameter of each insulating particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary insulating particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each insulating particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the insulating particles is preferably calculated using a particle size distribution measuring device. When the particle diameter of the insulating particles in the conductive particles is measured, it can be measured, for example, as follows.
[0181] Conductive particles are added to Kulzer's Technovit 4000 so that the content is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. A cross section of the conductive particles is cut out using an ion milling device (Hitachi High-Technologies' IM4000) so as to pass through the center of the dispersed conductive particles in the resin body for inspection. Then, 50 conductive particles are randomly selected using a field emission scanning electron microscope (FE-SEM), and the insulating particles of each conductive particle are observed. The particle diameter of the insulating particles in each conductive particle is measured, and the particle diameter of the insulating particles is determined by arithmetic averaging.
[0182] (Conductive materials) The conductive material according to the present invention includes conductive particles and a binder. The conductive particles are the conductive particles described above. The conductive particles are preferably dispersed in a binder and used, and are preferably dispersed in a binder and used as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive material is preferably used for electrical connection between electrodes. The conductive material is preferably a conductive material for circuit connection. Since the conductive material uses the conductive particles described above, the connection resistance between electrodes can be more effectively reduced, and the occurrence of aggregation between conductive particles can be more effectively suppressed. Since the conductive material uses the conductive particles described above, when electrodes are electrically connected, the conduction reliability can be more effectively increased, and further, the insulation reliability can be more effectively increased.
[0183] The binder is not particularly limited. Known insulating resins and solvents can be used as the binder. The binder preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. Examples of the curable component include a photocurable component and a thermosetting component. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent.
[0184] Examples of the binder include vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers, elastomers, solvents, etc. The binders may be used alone or in combination of two or more.
[0185] Examples of the vinyl resin include vinyl acetate resin, acrylic resin, and styrene resin. Examples of the thermoplastic resin include polyolefin resin, ethylene-vinyl acetate copolymer, and polyamide resin. Examples of the curable resin include epoxy resin, urethane resin, polyimide resin, and unsaturated polyester resin. The curable resin may be a room temperature curable resin, a thermosetting resin, a photocurable resin, or a moisture curable resin. The curable resin may be used in combination with a curing agent. Examples of the thermoplastic block copolymer include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated product of styrene-butadiene-styrene block copolymer, and hydrogenated product of styrene-isoprene-styrene block copolymer. Examples of the elastomer include styrene-butadiene copolymer rubber, and acrylonitrile-styrene block copolymer rubber.
[0186] Examples of the solvent include water and organic solvents. Organic solvents are preferred because they can be easily removed. Examples of the organic solvent include alcohol compounds such as ethanol, ketone compounds such as acetone, methyl ethyl ketone, and cyclohexanone, aromatic hydrocarbon compounds such as toluene, xylene, and tetramethylbenzene, glycol ether compounds such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and tripropylene glycol monomethyl ether, ester compounds such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate, aliphatic hydrocarbon compounds such as octane and decane, and petroleum-based solvents such as petroleum ether and naphtha.
[0187] In addition to the conductive particles and the binder, the conductive material may contain various additives such as, for example, a filler, an extender, a softener, a plasticizer, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.
[0188] The method for dispersing the conductive particles in the binder can be a conventionally known dispersion method, and is not particularly limited. Examples of the method for dispersing the conductive particles in the binder include the following methods. A method in which the conductive particles are added to the binder and then kneaded and dispersed with a planetary mixer or the like. A method in which the conductive particles are uniformly dispersed in water or an organic solvent using a homogenizer or the like, then added to the binder, and then kneaded and dispersed with a planetary mixer or the like. A method in which the binder is diluted with water or an organic solvent, then the conductive particles are added, and then kneaded and dispersed with a planetary mixer or the like.
[0189] The viscosity (η25) of the conductive material at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, and preferably 400 Pa·s or less, more preferably 300 Pa·s or less. When the viscosity of the conductive material at 25°C is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the connection reliability between the electrodes can be more effectively improved. The viscosity (η25) can be appropriately adjusted by the types and amounts of the components.
[0190] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 5 rpm.
[0191] The conductive material according to the present invention can be used as a conductive paste, a conductive film, or the like. When the conductive material according to the present invention is a conductive film, a film not containing conductive particles may be laminated on a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.
[0192] In 100% by weight of the conductive material, the content of the binder is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, particularly preferably 70% by weight or more, and is preferably 99.99% by weight or less, more preferably 99.9% by weight or less. When the content of the binder is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the connection reliability between the electrodes can be more effectively increased.
[0193] In 100% by weight of the conductive material, the content of the conductive particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and is preferably 80% by weight or less, more preferably 60% by weight or less, even more preferably 40% by weight or less, particularly preferably 20% by weight or less, and most preferably 10% by weight or less. When the content of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the connection reliability between the electrodes can be more effectively increased.
[0194] Flux: The conductive material may contain a flux. By using the flux, when the electrodes are electrically connected, the reliability of the electrical connection can be more effectively improved. The flux is not particularly limited. As the flux, a flux generally used for solder joints or the like can be used.
[0195] Examples of the flux include zinc chloride, a mixture of zinc chloride and an inorganic halide, a mixture of zinc chloride and an inorganic acid, a molten salt, phosphoric acid, a derivative of phosphoric acid, an organic halide, hydrazine, an amine compound, an organic acid, and rosin, etc. Only one type of the flux may be used, or two or more types may be used in combination.
[0196] The molten salt may be ammonium chloride or the like. The organic acid may be lactic acid, citric acid, stearic acid, glutamic acid, glutaric acid, or the like. The rosin may be activated rosin or non-activated rosin. The flux is preferably an organic acid having two or more carboxyl groups, or rosin. The flux may be an organic acid having two or more carboxyl groups, or rosin. The use of an organic acid having two or more carboxyl groups, or rosin, further increases the reliability of conduction between electrodes.
[0197] Examples of the organic acid having two or more carboxyl groups include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid.
[0198] Examples of the amine compound include cyclohexylamine, dicyclohexylamine, benzylamine, benzhydrylamine, imidazole, benzimidazole, phenylimidazole, carboxybenzimidazole, benzotriazole, and carboxybenzotriazole.
[0199] The rosin is a rosin containing abietic acid as a main component. Examples of the rosin include abietic acid and acrylic modified rosin. The flux is preferably a rosin, more preferably abietic acid. The use of this preferred flux further increases the reliability of electrical continuity between electrodes.
[0200] The activation temperature (melting point) of the flux is preferably 50°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher, and is preferably 200°C or lower, more preferably 190°C or lower, even more preferably 160°C or lower, even more preferably 150°C or lower, and even more preferably 140°C or lower. When the activation temperature of the flux is above the lower limit and below the upper limit, the flux effect is more effectively exerted, and the electrical reliability between the electrodes can be more effectively improved. The activation temperature (melting point) of the flux is preferably 80°C or higher and 190°C or lower. It is particularly preferable that the activation temperature (melting point) of the flux is 80°C or higher and 140°C or lower.
[0201] Examples of the flux having an active temperature (melting point) of 80°C or higher and 190°C or lower include dicarboxylic acids such as succinic acid (melting point 186°C), glutaric acid (melting point 96°C), adipic acid (melting point 152°C), pimelic acid (melting point 104°C), and suberic acid (melting point 142°C), benzoic acid (melting point 122°C), and malic acid (melting point 130°C), etc.
[0202] The flux preferably has a boiling point of 200° C. or lower.
[0203] The flux may be dispersed in the conductive material or attached to the surface of the conductive particles, and from the viewpoint of more effectively increasing the conduction reliability when the electrodes are electrically connected, the flux is preferably attached to the surface of the conductive particles.
[0204] From the viewpoint of more effectively increasing the electrical conductivity reliability, the flux is preferably a salt of an acid compound and a base compound.
[0205] The acid compound is preferably an organic compound having a carboxyl group. Examples of the acid compound include aliphatic carboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, citric acid, and malic acid, cyclic aliphatic carboxylic acids such as cyclohexyl carboxylic acid and 1,4-cyclohexyl dicarboxylic acid, and aromatic carboxylic acids such as isophthalic acid, terephthalic acid, trimellitic acid, and ethylenediaminetetraacetic acid. From the viewpoint of more effectively increasing the electrical reliability, the acid compound is preferably glutaric acid, cyclohexyl carboxylic acid, or adipic acid.
[0206] The basic compound is preferably an organic compound having an amino group. Examples of the basic compound include diethanolamine, triethanolamine, methyldiethanolamine, ethyldiethanolamine, cyclohexylamine, dicyclohexylamine, benzylamine, benzhydrylamine, 2-methylbenzylamine, 3-methylbenzylamine, 4-tert-butylbenzylamine, N-methylbenzylamine, N-ethylbenzylamine, N-phenylbenzylamine, N-tert-butylbenzylamine, N-isopropylbenzylamine, N,N-dimethylbenzylamine, imidazole compounds, and triazole compounds. From the viewpoint of more effectively increasing the reliability of electrical conduction, the basic compound is preferably benzylamine.
[0207] The content of the flux is preferably 0.5% by weight or more, preferably 30% by weight or less, and more preferably 25% by weight or less, based on 100% by weight of the conductive material. When the content of the flux is equal to or more than the lower limit and equal to or less than the upper limit, an oxide film is more unlikely to form on the surface of the electrode, and further, the oxide film formed on the surface of the electrode can be more effectively removed.
[0208] (Connection structure) The connection structure according to the present invention comprises a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection part connecting the first connection target member and the second connection target member. In the connection structure according to the present invention, the connection part is formed of conductive particles or is formed of a conductive material containing the conductive particles and a binder. In the connection structure according to the present invention, the conductive particles are the conductive particles described above. In the connection structure according to the present invention, the first electrode and the second electrode are electrically connected by the conductive particles.
[0209] FIG. 9 is a front cross-sectional view that typically shows a connection structure using conductive particles according to a fourth embodiment of the present invention.
[0210] A connection structure 81 shown in Fig. 9 includes a first connection target member 82, a second connection target member 83, and a connection portion 84 connecting the first connection target member 82 and the second connection target member 83. The connection portion 84 is formed of a conductive material containing conductive particles 21. Note that in Fig. 9, the conductive particles 21 are shown diagrammatically for convenience of illustration.
[0211] The first connection target member 82 has a plurality of first electrodes 82a on its surface (upper surface). The second connection target member 83 has a plurality of second electrodes 83a on its surface (lower surface). The first electrodes 82a and the second electrodes 83a are electrically connected by one or more conductive particles 21. Therefore, the first connection target member 82 and the second connection target member 83 are electrically connected by the conductive particles 21.
[0212] The method for manufacturing the connection structure is not particularly limited. One example of the method for manufacturing the connection structure includes a method in which the conductive material is placed between the first connection target member and the second connection target member to obtain a laminate, and then the laminate is heated and pressurized. By heating and pressing, the conductive part (solder part) of the conductive particles 21 melts, and the electrodes are electrically connected by the conductive particles 21. Furthermore, when the binder contains a thermosetting compound, the thermosetting compound is thermally cured, and the connection part that connects the first connection target member and the second connection target member is formed by the thermally cured hardened product. The pressure of the pressurization is 9.8×10 4 Pa~4.9×10 6 The heating temperature is 120°C to 220°C.
[0213] FIG. 10 is an enlarged front cross-sectional view that illustrates a schematic view of a connection portion between a conductive particle and an electrode in the connection structure shown in FIG.
[0214] 10, in the connection structure 81, the laminate is heated and pressurized, whereby the second conductive portion (solder portion) 22B of the conductive particle 21 melts, and then the melted second conductive portion (solder portion) portion 22Ba is in sufficient contact with the first electrode 82a and the second electrode 83a. That is, by using the conductive particle 21 whose surface layer is a solder portion, the contact area between the conductive particle 21 and the first electrode 82a and the second electrode 83a is larger than when using a conductive particle whose surface layer is a metal such as nickel, gold, or copper. This increases the conduction reliability of the connection structure 81.
[0215] The first and second connection target members are not particularly limited. Specific examples of the first and second connection target members include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, as well as electronic components such as resin films, printed circuit boards, flexible printed circuit boards, flexible flat cables, rigid flexible boards, glass epoxy boards, and glass boards. The first and second connection target members are preferably electronic components.
[0216] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, silver electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.
[0217] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0218] Example 1 Preparation of conductive particles 1: As the base particles (S1), divinylbenzene copolymer resin particles ("Micropearl SP-220, particle diameter 20 μm" manufactured by Sekisui Chemical Co., Ltd.) were prepared.
[0219] 10 parts by weight of base particles (S1) were dispersed in 100 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution using an ultrasonic disperser, and the solution was filtered to extract the base particles (S1). Next, the base particles (S1) were added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surface of the base particles (S1). The base particles (S1) with the activated surface were thoroughly washed with water, and then added to 500 parts by weight of distilled water and dispersed to obtain a suspension (A1).
[0220] The suspension (A1) was placed in a solution containing 25 g / L of nickel sulfate, 15 ppm of thallium nitrate, and 10 ppm of bismuth nitrate to obtain a particle mixture (B1).
[0221] Also, a nickel plating solution (C1) (pH 5.5) containing 100 g / L of nickel sulfate, 40 g / L of sodium hypophosphite, 15 g / L of sodium citrate, 25 ppm of thallium nitrate, and 10 ppm of bismuth nitrate was prepared.
[0222] In addition, as an electroless tin plating solution for forming solder grains, a tin plating solution (D1) was prepared by adjusting the pH of a mixture containing 15 g / L of tin sulfate, 45 g / L of ethylenediaminetetraacetic acid, and 1.5 g / L of phosphinic acid to 8.5 with sodium hydroxide.
[0223] In addition, a reducing solution (E1) was prepared by adjusting a solution containing 5 g / L of sodium borohydride to pH 10.0 with sodium hydroxide.
[0224] The nickel plating solution (C1) was gradually dropped into the particle mixture (B1) at 50°C in which the particles were dispersed, to perform electroless nickel plating. The nickel plating solution (C1) was dropped at a dropping speed of 12.5 mL / min for a dropping time of 30 minutes to perform electroless nickel plating (Ni plating step). In this way, a particle mixture (F1) was obtained, which contained particles having a nickel-phosphorus alloy conductive portion as a first conductive portion on the surface of the base particle S1.
[0225] Then, the particle mixture (F1) was filtered to take out the particles, and the particles were washed with water to obtain particles having nickel-phosphorus alloy conductive parts disposed on the surfaces of the base particles S1. After the particles were thoroughly washed with water, they were added to 500 parts by weight of distilled water and dispersed to obtain a particle mixture (G1).
[0226] Next, the tin plating solution (D1) was gradually added to the particle mixture (G1) at 60°C in which the particles were dispersed. Then, the reduction solution (E1) was dropped to perform electroless tin plating. The reduction solution (E1) was dropped at a rate of 0.5 mL / min for 40 minutes, and then stirred for 10 minutes to perform electroless tin plating. Then, the particles were removed by filtration, washed with water, and dried to obtain conductive particles 1 having nickel-phosphorus alloy conductive parts and tin conductive parts (solder particles) (total thickness of conductive parts in parts without solder particles: 0.1 μm, height of solder particles: 0.6 μm) on the surface of the base particle S1.
[0227] Example 2 Preparation of conductive particles 2: The suspension (A1) of Example 1 was prepared.
[0228] The above suspension (A1) was placed in a solution containing 2 g / L of potassium gold cyanide, 10 g / L of sodium citrate, 0.5 g / L of ethylenediaminetetraacetic acid, and 5 g / L of sodium hydroxide to obtain a particle mixture (B2).
[0229] In addition, a gold plating solution (C2) (pH 8.0) containing 10 g / L potassium gold cyanide, 20 g / L sodium citrate, 5 ppm thallium nitrate, 3.0 g / L ethylenediaminetetraacetic acid, 20 g / L sodium hydroxide, and 10 g / L dimethylamine borane was prepared as an electroless gold plating solution.
[0230] In addition, the tin plating solution (D1) and the reducing solution (E1) of Example 1 were prepared as tin solutions for forming solder grains.
[0231] The gold plating solution (C2) was gradually dropped into the particle mixture (B2) at 60°C in which the particles were dispersed, to perform electroless gold plating. The gold plating solution (C2) was dropped at a rate of 2 mL / min for a drop time of 45 minutes, to perform electroless gold plating. In this way, a particle mixture (D2) was obtained, which contained particles having gold metal portions disposed as first conductive portions on the surfaces of the base particles S1.
[0232] The particle mixture (D2) was then filtered to remove the particles, which were then washed with water to obtain particles having gold conductive portions disposed on the surfaces of the base particles S1. After thoroughly washing the particles, the particles were added to 500 parts by weight of distilled water and dispersed to obtain a particle mixture (E2).
[0233] Thereafter, solder particles were formed using the tin plating solution (D1) and the reducing solution (E1) in the same manner as in Example 1, and a particle mixture (F2) containing particles in which solder particles were formed on gold conductive parts was obtained.
[0234] The particle mixture (F2) was then filtered to remove the particles, which were then washed with water to obtain particles having gold conductive portions disposed on the surfaces of the base particles S1 and solder particles formed thereon. After thoroughly washing the particles, the particles were added to 500 parts by weight of distilled water and dispersed to obtain a particle mixture (G2).
[0235] Next, the gold plating solution (C2) was gradually dropped into the particle mixture (G2) at 60°C in which the particles were dispersed, to perform electroless gold plating. The gold plating solution (C2) was dropped at a rate of 1 mL / min for a period of 1 minute, and electroless gold plating was performed. The particles were then removed by filtration, washed with water, and dried to obtain conductive particles 2 having a gold conductive portion (total conductive portion thickness: 0.1 μm) on the surface of the base particle S1 and a gold thin film (metal film thickness: 0.01 μm) on the solder grains (solder grain height: 0.6 μm).
[0236] Example 3 Preparation of conductive particles 3: Conductive particles having a nickel-phosphorus alloy conductive portion and solder particles on a base particle were obtained in the same manner as in Example 1. The obtained conductive particles were added to 500 parts by weight of distilled water and dispersed to obtain a suspension (A3).
[0237] In addition, a silver plating solution (B3) was prepared as an electroless silver plating solution by adjusting the pH of a mixture of 30 g / L of silver nitrate, 100 g / L of succinimide, and 20 g / L of formaldehyde with ammonia water to 8.0.
[0238] The suspension (A3) at 60° C. was mixed and dispersed in the silver plating solution (B3) to obtain a particle mixture solution (C3).
[0239] Next, the silver plating solution (B3) was gradually dropped into the particle mixture (C3) at 60°C in which the particles were dispersed, to perform electroless silver plating. The silver plating solution (B3) was dropped at a rate of 10 mL / min for a period of 10 minutes, and electroless plating was performed. The particles were then removed by filtration, washed with water, and dried to obtain conductive particles 3 having a nickel-phosphorus alloy conductive part (total conductive part thickness: 0.1 μm) on the surface of the base particle S1 and a silver thin film (metal film thickness: 0.01 μm) on the solder particles (solder particle height: 0.6 μm).
[0240] Example 4 Preparation of conductive particles 4: The suspension (A3) of Example 3 was prepared.
[0241] In addition, a silver solution (B4) was prepared by adjusting the pH of a mixture containing 1 g / L silver nitrate, 30 g / L ethylenediaminetetraacetic acid, and 20 ppm polyethylene glycol (molecular weight 6000) to 11 with sodium hydroxide.
[0242] In addition, a solution containing 10 g / L of sodium borohydride and 40 g / L of sodium hydroxide was prepared as a reducing solution (D4) for forming a metal colloid precipitate.
[0243] Moreover, the suspension (A3) was mixed and dispersed in the silver solution (B4) to obtain a particle mixture (C4).
[0244] Next, 1 part by weight of the above-mentioned reducing solution (D4) for forming a metal colloid precipitate was added to the particle mixture (C4) at 25°C in which the particles were dispersed, and the mixture was stirred for 10 minutes. After that, the particles were taken out by filtration, washed with water, and dried to obtain conductive particles 4 having silver colloid precipitates (particle diameter of the metal colloid precipitates: 0.02 μm) on the surfaces of the conductive particles.
[0245] Example 5 Preparation of conductive particles 5: The suspension (A3) of Example 3 was prepared.
[0246] In addition, an indium solution (B5) was prepared by adjusting a mixed solution containing 5 g / L of indium chloride, 40 g / L of ethylenediaminetetraacetic acid, and 0.01 g / L of polyvinylpyrrolidone to pH 10 with sodium hydroxide.
[0247] As a reducing liquid, the reducing liquid for forming a colloidal precipitate (D4) of Example 4 was prepared.
[0248] The suspension (A3) was mixed and dispersed in the indium solution (B5) to obtain a particle mixture (C5).
[0249] 10 parts by weight of the above-mentioned reducing solution for forming a metal colloid precipitate (D4) was added to the particle mixture (C5) at 50° C. in which the particles were dispersed, and the mixture was stirred for 60 minutes. After that, the particles were taken out by filtration, washed with water, and dried to obtain conductive particles 5 having an indium colloid precipitate (particle diameter of the metal colloid precipitate: 0.01 μm) on the surface of the conductive particles.
[0250] Example 6 Preparation of conductive particles 6: The suspension (A3) of Example 3 was prepared.
[0251] In addition, a copper solution (B6) was prepared by adjusting the pH of a mixed solution containing 10 g / L of copper sulfate pentahydrate, 40 g / L of ethylenediaminetetraacetic acid, and 0.1 g / L of polyvinylpyrrolidone to 9.0 with sodium hydroxide.
[0252] As a reducing liquid, the reducing liquid (D4) for forming a metal colloid precipitate of Example 4 was prepared.
[0253] The suspension (A3) was mixed and dispersed in the copper solution (B6) to obtain a particle mixture (C6).
[0254] Five parts by weight of the reducing solution (D4) for forming a metal colloid precipitate was added to the particle mixture (C6) at 25° C. in which the particles were dispersed, and the mixture was stirred for 60 minutes. The particles were then taken out by filtration, washed with water, and dried to obtain conductive particles 6 having copper colloid precipitates (particle diameter of the metal colloid precipitates: 0.01 μm) on the surfaces of the conductive particles.
[0255] Example 7 Preparation of conductive particles 7: As an electroless tin plating solution for forming solder grains, a tin plating solution (B7) was prepared by adjusting the pH of a mixture containing 15 g / L of tin sulfate, 45 g / L of ethylenediaminetetraacetic acid, 1.5 g / L of phosphinic acid, and 10 g / L of trehalose dihydrate to 9.0 with sodium hydroxide.
[0256] Conductive particles 7 were obtained in the same manner as in Example 1, except that the electroless tin plating solution for forming solder grains (D1) was changed to the electroless tin plating solution for forming solder grains (B7) (total thickness of the conductive part in the part without solder grains: 0.2 μm, height of solder grains: 0.9 μm).
[0257] Example 8 Preparation of conductive particles 8: (1) Preparation of silicone oligomers In a 100 ml separable flask placed in a warm bath, 1 part by weight of 1,3-divinyltetramethyldisiloxane and 20 parts by weight of 0.5% by weight p-toluenesulfonic acid aqueous solution were placed. After stirring at 40°C for 1 hour, 0.05 parts by weight of sodium hydrogen carbonate was added. Then, 10 parts by weight of dimethoxymethylphenylsilane, 49 parts by weight of dimethyldimethoxysilane, 0.6 parts by weight of trimethylmethoxysilane, and 3.6 parts by weight of methyltrimethoxysilane were added and stirred for 1 hour. Then, 1.9 parts by weight of 10% by weight potassium hydroxide aqueous solution was added, and the temperature was raised to 85°C, and the reaction was carried out by stirring for 10 hours while reducing the pressure with an aspirator. After the reaction was completed, the pressure was returned to normal pressure and cooled to 40°C, 0.2 parts by weight of acetic acid was added, and the mixture was left to stand in a separatory funnel for 12 hours or more. The lower layer after the two-layer separation was taken out and purified with an evaporator to obtain a silicone oligomer.
[0258] (2) Preparation of silicone particle materials (including organic polymers) 0.5 parts by weight of tert-butyl-2-ethylperoxyhexanoate (polymerization initiator, NOF Corp.'s "Perbutyl O") was dissolved in 30 parts by weight of the obtained silicone oligomer to prepare solution A. 0.8 parts by weight of a 40% by weight aqueous solution of triethanolamine lauryl sulfate (emulsifier) and 80 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol (polymerization degree: about 2000, saponification degree: 86.5-89 mol%, Nippon Synthetic Chemical Industry Co., Ltd.'s "Gosenol GH-20") were mixed in 150 parts by weight of ion-exchanged water to prepare solution B. After putting the solution A into a separable flask placed in a warm bath, the solution B was added. Then, emulsification was performed using a Shirasu Porous Glass (SPG) membrane (average pore size: about 1 μm). Then, the temperature was raised to 85° C., and polymerization was performed for 9 hours. The entire amount of particles after polymerization was washed with water by centrifugation, and freeze-dried. After drying, the particle aggregates were pulverized in a ball mill until the desired ratio (average secondary particle size / average primary particle size) was achieved, yielding silicone particles (base particle S2) with a particle size of 3.0 μm.
[0259] Conductive particles 8 were obtained in the same manner as in Example 1, except that the base particle S1 was changed to the base particle S2.
[0260] Example 9 Preparation of conductive particles 9: Silicone particles (base particle S3) having a particle size of 3.0 μm were obtained in the same manner as in Example 8, except that a silicone oil terminated in acryl ("X-22-2445" manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of the silicone oligomer.
[0261] Conductive particles 9 were obtained in the same manner as in Example 1, except that the base particle S1 was changed to the base particle S3.
[0262] Example 10 Preparation of conductive particles 10: Base particle S4, which differs from base particle S1 only in particle size, was prepared. The particle size was 3.0 μm.
[0263] Conductive particles 10 were obtained in the same manner as in Example 1, except that the base particle S1 was changed to the base particle S4.
[0264] Example 11 Preparation of conductive particles 11: Base particle S5, which differs from base particle S1 only in particle size, was prepared. The particle size was 10.0 μm.
[0265] Conductive particles 11 were obtained in the same manner as in Example 1, except that the base particle S1 was changed to the base particle S5.
[0266] Example 12 Preparation of conductive particles 12: Base particle S6, which differs from base particle S1 only in particle size, was prepared. The particle size was 35.0 μm.
[0267] Conductive particles 12 were obtained in the same manner as in Example 1, except that the base particle S1 was changed to the base particle S6.
[0268] Example 13 Preparation of conductive particles 13: The suspension (A1) of Example 1 was prepared.
[0269] A metallic nickel slurry (average particle diameter 150 nm) was prepared, and 1 part by weight was added to the above suspension (A1) over 3 minutes to obtain a particle mixture (B13) containing base particles S1 with a core material attached thereto. Then, electroless nickel plating was performed using the above nickel plating solution (C1) in the same manner as in Example 1 to obtain a particle mixture (F13) containing particles having a nickel-phosphorus alloy conductive part as a first conductive part on the surface of the base particle containing a metallic nickel core material.
[0270] The particle mixture (F13) was then filtered to extract the particles, which were then washed with water to obtain particles having nickel-phosphorus alloy conductive parts containing a metallic nickel core material disposed on the surface of the base particle S1. After thoroughly washing the particles, the particles were added to 500 parts by weight of distilled water and dispersed to obtain a particle mixture (G13).
[0271] Thereafter, in a manner similar to that of Example 1, solder particles were formed using the tin plating solution (D1) and the reducing solution (E1), and a particle mixture (H13) was obtained containing particles in which solder particles were formed on nickel-phosphorus alloy conductive parts.
[0272] The particles were then extracted by filtration, washed with water, and dried to obtain conductive particles 13 having a nickel-phosphorus alloy conductive portion containing a core material on the surface of the base particle S1 (total thickness of the conductive portion in the portion without the core material: 0.1 μm) and solder grains (height of the solder grains: 0.6 μm).
[0273] Example 14 Preparation of conductive particles 14: A titanium oxide particle slurry (average particle diameter: 150 nm) was prepared.
[0274] Conductive particles 14 were obtained in the same manner as in Example 13, except that the metallic nickel particle slurry was changed to the titanium oxide particle slurry.
[0275] Example 15 Preparation of conductive particles 15: An alumina particle slurry (average particle size: 150 nm) was prepared.
[0276] Conductive particles 15 were obtained in the same manner as in Example 13, except that the metallic nickel particle slurry was changed to the alumina particle slurry.
[0277] (Example 16) Preparation of conductive particles 16: A 1000 mL separable flask equipped with a four-neck separable cover, stirring blade, three-way cock, cooling tube and temperature probe was prepared. A monomer composition containing 100 mmol of methyl methacrylate, 1 mmol of N,N,N-trimethyl-N-2-methacryloyloxyethyl ammonium chloride and 1 mmol of 2,2'-azobis(2-amidinopropane) dihydrochloride was weighed into the separable flask so that the solid content was 5% by weight. The mixture was then stirred at 200 rpm and polymerized at 70°C for 24 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was freeze-dried to obtain insulating particles having ammonium groups on the surface, an average particle size of 220 nm and a CV value of 10%.
[0278] The insulating particles were dispersed in ion-exchanged water under ultrasonic irradiation to obtain a 10 wt % aqueous dispersion of the insulating particles.
[0279] 10 g of the conductive particles obtained in Example 1 were dispersed in 500 mL of ion-exchanged water, 4 g of the aqueous dispersion of insulating particles was added, and the mixture was stirred at room temperature for 6 hours. After filtering through a 30 μm mesh filter, the mixture was washed with methanol and dried to obtain conductive particles 16 having insulating particles attached thereto.
[0280] Observation with a scanning electron microscope (SEM) revealed that only one coating layer of insulating particles was formed on the surface of the conductive particle 16. Image analysis was used to calculate the coverage area of the insulating particles (i.e., the projected area of the particle diameter of the insulating particles) relative to an area of 2.5 μm from the center of the conductive particle 16, and the coverage rate was 30%.
[0281] (Example 17) Preparation of conductive particles 17: In Example 1, except that the dripping time of the reducing liquid (E1) was changed to 20 minutes, a conductive particle 17 was obtained in the same manner as in Example 1, which has a nickel-phosphorus alloy conductive portion and a tin conductive portion (solder grains) on the surface of the base particle S1 (total thickness of the conductive portion in the part where there are no solder grains: 0.1 μm, height of the solder grains: 0.3 μm).
[0282] Comparative Example 1 Preparation of conductive particles A: In the same manner as in Example 1, a particle mixture (G1) was obtained.
[0283] In addition, a tin plating solution (d1) was prepared as an electroless tin plating solution by adjusting the pH of a mixed solution containing 20 g / L of tin chloride, 50 g / L of nitrilotriacetic acid, 2 g / L of thiourea, 1 g / L of thiomalic acid, 7.5 g / L of ethylenediaminetetraacetic acid, and 15 g / L of titanium trichloride with sulfuric acid to 7.0.
[0284] Next, the above tin plating solution (d1) was gradually dropped into the particle mixture (G1) at 70°C in which the particles were dispersed, to perform electroless tin plating. The tin plating solution (d1) was dropped at a rate of 30 mL / min for a period of 20 minutes, to perform electroless tin plating. The particles were then removed by filtration, washed with water, and dried to obtain conductive particles A having a nickel-phosphorus alloy conductive portion and a tin conductive portion (total thickness of conductive portion: 0.3 μm) on the surface of the base particle S1.
[0285] Comparative Example 2 Preparation of conductive particles B: A particle mixture (G13) was prepared in the same manner as in Example 13.
[0286] In addition, the electroless tin plating solution (d1) of Comparative Example 1 was prepared.
[0287] Electroless tin plating was performed in the same manner as in Comparative Example 1 to obtain conductive particles B having a nickel-phosphorus alloy conductive portion containing a core material and a tin conductive portion (total thickness of the conductive portion in the portion without the core material: 0.3 μm) on the surface of the base particle S1.
[0288] Comparative Example 3 Preparation of conductive particles C: In the same manner as in Example 1, a particle mixture (F1) was obtained.
[0289] Thereafter, the particle mixture (F1) was filtered to extract the particles, which were then washed with water and dried to obtain conductive particles C having a nickel-phosphorus alloy conductive portion (conductive portion thickness: 0.1 μm) disposed on the surface of the base particle S1.
[0290] (evaluation) (1) Metal diffusion state of conductive parts The obtained conductive particles were added to "Structbond XN-5A" manufactured by Mitsui Chemicals, Inc. so that the content was 10 wt %, and dispersed to prepare an anisotropic conductive paste.
[0291] A transparent glass substrate having a copper electrode pattern with an L / S of 200 μm / 200 μm on its upper surface was prepared, and a semiconductor chip having a gold electrode pattern with an L / S of 200 μm / 200 μm on its lower surface was prepared.
[0292] The anisotropic conductive paste immediately after preparation was applied to the transparent glass substrate to a thickness of 30 μm to form an anisotropic conductive paste layer. Next, the semiconductor chip was laminated on the anisotropic conductive paste layer so that the electrodes faced each other. Then, a pressure heating head was placed on the upper surface of the semiconductor chip while adjusting the temperature of the head so that the temperature of the anisotropic conductive paste layer was 250° C., and a pressure of 0.5 MPa was applied to harden the anisotropic conductive paste layer at 250° C. to obtain a connection structure.
[0293] The cross-section of the resulting connection structure was observed to determine the state of metal diffusion in the conductive portion.
[0294] Using a transmission electron microscope FE-TEM (JEOL Ltd. "JEM-2010FEF"), the contact area between the conductive particles and the copper electrode pattern and the gold electrode pattern was elementally mapped by an energy dispersive X-ray analyzer (EDX) to observe the diffusion state of the conductive part. The diffusion state of the conductive part was judged according to the following criteria.
[0295] [Criteria for judging the diffusion state of conductive parts] A: In the connection, the conductive part of the conductive particle is diffused with the copper electrode pattern and the gold electrode pattern. B: In the connection, the conductive part of the conductive particles does not undergo metal diffusion with the copper electrode pattern and the gold electrode pattern.
[0296] (2) Melted and deformed state of conductive parts The connection structure obtained in the evaluation of (1) above was prepared. The prepared connection structure was placed in Kulzer's "Technovit 4000" and cured to prepare a resin body for embedding the connection structure for inspection. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the center of the connection structure in the resin body for inspection.
[0297] Then, the cross section of the obtained connection structure was observed using a field emission scanning electron microscope (FE-SEM) to confirm whether the conductive part of the conductive particles had been melted, deformed, and then solidified. The melt-deformed state of the conductive part was judged according to the following criteria.
[0298] [Criteria for determining the melting and deformation state of conductive parts] A: The conductive part is melted, deformed, and then solidified. B: The conductive part is not melted or deformed.
[0299] (3) Bonding condition of conductive parts The connection structure obtained in the evaluation of (1) above was prepared. The prepared connection structure was placed in Kulzer's "Technovit 4000" and cured to prepare a resin body for embedding the connection structure for inspection. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the center of the connection structure in the resin body for inspection.
[0300] The cross-section of the resulting connection structure was observed using a field-effect electron microscope (FE-SEM) to confirm the bonding state of the conductive portion. The bonding state of the conductive portion was evaluated according to the following criteria.
[0301] [Criteria for determining the bonding condition of conductive parts] A: In the connection part, the conductive part of 5 or more particles out of 10 conductive particles melts, deforms, and then solidifies, bonding with the electrode. B: In the connection part, the conductive part of 1 to less than 5 particles out of 10 conductive particles melts, deforms, and then solidifies to bond with the electrode. C: In the connection area, none of the 10 conductive particles were melted or deformed, and the conductive part was bonded to the electrode only by metal diffusion. D: In the connection, none of the 10 conductive particles are joined.
[0302] (4) The area of the part containing solder (solder grains) out of the total surface area of the base material particle (100%) (coverage rate of solder (solder grains)) For the obtained conductive particles, the area of the part where the solder was located out of the total surface area of the base particle (100%) was calculated. The above coverage (solder coverage) was calculated by performing SEM-EDX analysis of the cross section of the conductive particle, performing element mapping, and performing image analysis.
[0303] (5) Particle size of conductive particles The particle size of the obtained conductive particles was calculated using a particle size distribution measuring device (Multisizer 4 manufactured by Beckman Coulter, Inc.) Specifically, the particle sizes of about 100,000 conductive particles were measured and the average value was calculated.
[0304] (6) Thickness of conductive part The obtained conductive particles were added to Kulzer's "Technovit 4000" so that the content was 30% by weight, and dispersed to prepare an embedding resin for testing. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the center of the conductive particles dispersed in the embedding resin for testing.
[0305] Then, ten conductive particles were randomly selected and the conductive part of each conductive particle was observed using a field emission transmission electron microscope (FE-TEM) (JEM-ARM200F manufactured by JEOL Ltd.) The thickness of the part where the conductive part had the maximum thickness was measured for each conductive particle, and the arithmetic average of these was taken as the thickness of the conductive part.
[0306] (7) Aggregation of conductive particles The obtained conductive particles were observed to confirm whether or not agglomeration of the conductive particles occurred. The agglomeration of the conductive particles was judged under the following conditions.
[0307] [Criteria for determining agglomeration of conductive particles] ○○: No aggregation of conductive particles occurs ○: Small agglomerations of conductive particles are slightly occurring. △: Among the conductive particle agglomerations, a small amount of large agglomerations occurred. ×: Aggregation of conductive particles occurs
[0308] Small agglomerates refer to agglomerates of four or fewer particles connected by a plating film, and large agglomerates refer to agglomerates of five or more particles connected by a plating film.
[0309] (8) Height of solder particles The obtained conductive particles were added to Kulzer's Technovit 4000 so that the content of the conductive particles was 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's IM4000) so as to pass through the center of the conductive particles dispersed in the resin body for inspection.
[0310] Then, using a field emission scanning electron microscope (FE-SEM), the conductive particles were randomly selected and the solder grains on the conductive particles were observed. The heights of the solder grains were measured at five points on the conductive particles and the arithmetic average of these measurements was determined as the height of the solder grains.
[0311] (9) Aspect ratio of solder grains The aspect ratio of a solder grain is the ratio of the height of a solder grain to the width of the solder grain (height of solder grain / width of solder grain), and was calculated from the height and width of the solder grain.
[0312] The width of the solder grains was measured as follows.
[0313] The obtained conductive particles were added to Kulzer's Technovit 4000 so that the content of the conductive particles was 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's IM4000) so as to pass through the center of the conductive particles dispersed in the resin body for inspection.
[0314] Then, a field emission scanning electron microscope (FE-SEM) was used to randomly select conductive particles and observe the solder grains on the conductive particles. The widths of the solder grains were measured at five points on the conductive particles and the arithmetic average was calculated to determine the width of the solder grains. The aspect ratio of the solder grains (solder grain height / solder grain width) was calculated from the obtained solder grain height and width.
[0315] (10) The area of the portion containing metal colloid deposits or metal film out of the total surface area of the solder particle (coverage rate of metal colloid deposits or metal film) For the obtained conductive particles, the area of the part where the metal colloid deposit or metal film was present out of the total surface area of the solder particle (coverage rate of the metal colloid deposit or metal film) was calculated. The above coverage rate (coverage rate of the metal colloid deposit or metal film) was calculated by performing element mapping by SEM-EDX analysis of the cross section of the solder particle in the conductive particle and performing image analysis.
[0316] The results are shown in Tables 1 to 4 below.
[0317] [Table 1]
[0318] [Table 2]
[0319] [Table 3]
[0320] [Table 4] [Explanation of symbols]
[0321] 1...Conductive particles 2...Base material particles 3...Conductive part 3A…First conductive part 3B: Second conductive part (solder part) 11...Conductive particles 12...Conductive part 12A...1a conductive part 12B...1b conductive part 12C: Second conductive part (solder part) 21...Conductive particles 22...Conductive part 22A…First conductive part 22B: Second conductive part (solder part) 22Ba…Melted second conductive part (solder part) 31...Conductive particles 32...Conductive part 32A…First conductive part 32B: Second conductive part (solder part) 32C…Third conductive part 41...Conductive particles 42...Conductive part 42A…First conductive part 42B: Second conductive part (solder part) 43...Metal colloid precipitate 51...Conductive particles 52...Conductive part 52A...1a conductive part 52B...1b conductive part 52C: Second conductive part (solder part) 53...Metal colloid deposits 61...Conductive particles 62...Conductive part 62A…First conductive part 62B: Second conductive part (solder part) 63...Metal film 71...Conductive particles 72...Conductive part 72A...1a conductive part 72B...1b conductive part 72C: Second conductive part (solder part) 73...Metal film 81...Connection structure 82...First connection target member 82a...first electrode 83...Second connecting member 83a...second electrode
Claims
1. A base particle; A conductive portion is disposed on the surface of the base particle, The conductive portion contains a component capable of metal diffusion at 400° C. or less, or the conductive portion is melt-deformable at 400° C. or less, the conductive portion has a solder portion, A conductive particle, wherein the area of the portion where the solder portion is present is 99% or less of the total surface area (100%) of the base particle.
2. The conductive particle according to claim 1 , wherein the solder portion is a solder grain.
3. The conductive particle according to claim 2 , wherein the material of the solder grain comprises an alloy containing tin, is pure tin, or contains tin in a state different from the alloy containing tin and different from pure tin.
4. The conductive particles according to claim 3 , wherein the material of the solder grains is pure tin.
5. The conductive particles according to any one of claims 2 to 4, wherein the height of the solder grains is 10 nm or more and 10 μm or less.
6. The conductive particles according to any one of claims 2 to 5, wherein the aspect ratio of the solder grains is 0.05 or more and 5 or less.
7. The conductive particle according to any one of claims 2 to 6, having a metal colloid deposit or a metal film on the outer surface of the solder grain.
8. The conductive particle according to claim 7 , wherein an area of the portion where the metal colloid deposit or the metal film is present is 5% or more and 100% or less of a total surface area (100%) of the solder grain.
9. 9. The conductive particle according to claim 7 or 8, wherein the metal species of the metal colloid deposit or the metal species of the metal film is nickel, cobalt, lead, gold, zinc, palladium, copper, silver, bismuth, or indium.
10. The conductive particles according to any one of claims 1 to 9, having a particle diameter of 0.5 µm or more and 500 µm or less.
11. The conductive particles and the binder are included. A conductive material, wherein the conductive particles are the conductive particles according to any one of claims 1 to 10.
12. a first connection target member having a first electrode on a surface thereof; a second connection target member having a second electrode on a surface thereof; a connection portion connecting the first connection target member and the second connection target member, the connection portion is formed of conductive particles or is formed of a conductive material containing the conductive particles and a binder, The conductive particles are the conductive particles according to any one of claims 1 to 10, A connection structure, wherein the first electrode and the second electrode are electrically connected by the conductive particles.
Citation Information
Patent Citations
Conductive material, method for producing conductive material, and connection structure
JP2018045906A
Metal atom-containing grain, connection material, connection structure, and method for producing connection structure
JP2018046010A
Conductive particles, conductive materials and connection structures
JP7614843B2
Metal-containing particle, connection material, connection structure, method for manufacturing connection structure, conduction inspection member, and conduction inspection device
WO2019059266A1
Structure and method for connecting electronic component
JP2000294997A